Crossing Thresholds in The House of the Seven Gables: Hawthorne’s Narrative Architecture and the Encounter with History - Woodard, Luke (Nathaniel Hawthorne Review, 2025)
ABSTRACT. This article examines the formal significance of the threshold trope in The House of the Seven Gables. While readers and critics alike have long noted the threshold’s thematic importance to the story, Luke Woodard reads the architectural image as a metaphor for the novel’s narrative structure. Just as the novel’s characters are constantly stepping back and forth across the literal thresholds of the Pyncheon-house, Hawthorne employs a variety of unconventional narrative techniques to dramatize the reader’s crossing into the fictional world of his story. In doing so, Hawthorne recreates for his audience a similar process to what Clifford and Holgrave undergo over the course of the story, urging the reader to move beyond a binary conception of past and present. In the final section of the article, the author argues that the House of the Seven Gables Settlement Association and Museum in Salem currently stands as both a result and continuation of Hawthorne’s narrative technique. Woodard’s approach sheds light on the extent to which the self-reflexive formal structures of Hawthorne’s fiction are connected to his work as a writer of historical romance.
Keywords: dept.eng

Introduction: The House of the Seven Gables in Ink, Wood, and Stone - Baraw, Charles (Nathaniel Hawthorne Review, 2025)
Best-selling author Alice Hoffman’s 2023 magic-realist-bio-fiction, The Invisible Hour, features a very visible Nathaniel Hawthorne as the romantic lead. Set in the twenty-first century and in Hawthorne’s time, the story unfolds in Concord, Salem, and the Berkshires, all places Hawthorne lived. At a crucial moment in the contemporary story, the protagonist, Mia Allen, flees her abusive stepfather, who has chased her from his fundamentalist cult in the Berkshires to New York City then to Concord and to Salem—her last hope of escape. Once there, she runs directly to the House of the Seven Gables. Mia believes she might return to her beloved author, if she can reach the house where he was born. It might be another portal to the past, like “Sleepy Hollow Cemetery” in Concord, where she first traveled back in time to meet Hawthorne. Unfortunately, when she gets to the museum on Turner Street, a summer intern, “who had written a paper on The House of the Seven Gables,” has already locked the gate (Hoffman 209).1 Visiting hours are over.I start my introduction to this special issue of the Nathaniel Hawthorne Review, “The House of the Seven Gables in Ink, Wood, and Stone,” with an example from a modern prequel to The Scarlet Letter to illustrate how a central paradox about the House persists to our day: the House of the Seven Gables is real and not real. In The Invisible Hour, Mia Allen runs toward one of the most popular cultural and literary tourist sites in the United States (voted “Best Historical Home Tour” in 2025 by Newsweek magazine). When Hoffman brings Mia to Salem, she can be confident that her novel’s readers may be among the more than one hundred thousand people who visit the museum each year. This is the House of the Seven Gables as a recognizable cultural icon, a vibrant contemporary institution and an engine of economic activity in Salem’s postindustrial economy. Or rather, this is the House of the Seven Gables in “Wood” and “Stone”: a complex of antiquarian buildings, gardens, and grounds—tangible, visitable, real.Yet once Hoffman gets Mia inside the gates of the museum, a haze, fog, or something intangible descends, and she promptly disappears from the twenty-first century—becoming invisible to the hapless intern—“and nothing was as it had appeared to be” (Hoffman 209). This is the House of the Seven Gables in “Ink”—a fiction whose magic derives from the afterlife of Hawthorne’s original text. Things happen there that we might not expect in a crowded house-museum tour. Hoffman’s House of the Seven Gables becomes a literary habitation: a house as metaphor, extending across time and space. Mia, too, becomes a symbolic figure and a contemporary embodiment of the ideal reader. She makes visible our metaphors for reading as immersion and imagined presence in a world elsewhere. Her love affair with Nathaniel Hawthorne dramatizes both the contemporary popularity of romance and the history of “author love” that scholars have recognized as a powerful aspect of canon formation and literary reception.2 Hoffman’s Hawthorne—a love-object and a romantic lead, a canonical author yet still unknown, a historical person and a fictional afterlife—is himself real and unreal.An ontological ambiguity between fact and fiction has characterized the reception of the house on Turner Street in Salem since it was first called the House of the Seven Gables (now the Turner-Ingersoll House, the centerpiece of The House of the Seven Gables Museum). Within the decade following Hawthorne’s death, his readers had made the house on Turner Street, along with “The Hawthorne House” (the birthplace on Union Street) and the Custom-House, a destination for literary pilgrimages. From the start, though, this popular mode of literary reception sparked a debate about the house’s status. George Parsons Lathrop takes a side in his 1876 Study of Hawthorne, acknowledging “some slight controversy as to the original of the visionary mansion” before denying misguided attempts to locate any original (235). In his “Introductory Note” to the 1883 Riverside edition of The House of the Seven Gables, Lathrop doubles-down against the “hundreds of pilgrims annually” who visit the Turner Street house and the “delusion that there must have been a single original House of the Seven Gables, framed by flesh-and-blood carpenters” (xiii, xii). In 1880 Thomas Franklin Hunt and Henry Morrill Batchelder published the first edition of the Visitors’ Guide to Salem,3 designed to capitalize on growing tourist interest in Salem. Hunt and Batchelder agreed with Lathrop, denying the existence of the House of the Seven Gables: “Inquiries are frequently made for ‘the House of the Seven Gables,’” and “it would be very pleasant to direct admirers of the great writer to such a house, but as a matter of fact none exists or ever has existed.” Despite the evident demand, the Guide would not indulge the fantasies of literary pilgrims, who insist on a standing, tangible original of Hawthorne’s fictive house. Nevertheless, the 1880 Guide observes that “Turner street is one of the oldest in the city,” and “the stranger will not find that his time has been wasted if he takes a stroll to the old house.” The “old house,” the Guide obligingly points out, “is the last house on the right-hand side going from Derby street,” helpful directions to a House of the Seven Gables that is curiously there and not there (47).By the time Henry James visited Salem in the fall of 1904, pilgrimages by literary tourists were thriving. The Upton family had hung out a sign on Turner Street, charged admission for tours of “The House of the Seven Gables,” and sold souvenirs. Frank Cousins had produced an attractive photo-collage, “Souvenir of Hawthorne’s House of the Seven Gables,” featuring what became iconic images of “Hawthorne,” “The Birthplace,” “The Old Pump,” “The House of the Seven Gables,” and the “Grimshawe House,” and sold many others at his Essex Street shop.4But the “slight controversy” between those who came to visit the house of wood and stone and those insisting it existed only in ink and imagination continued. Text from the 1880 Guide denying the existence of the House of the Seven Gables was reproduced and expanded in several more editions. Repeating an argument from 1895, the 1902 edition of the Visitors’ Guide to Salem (advertised as the “forty-fifth thousand”) states: “‘The House of the Seven Gables’ it is useless to search for, except within the covers of the fascinating book so named” (9). This edition, the most current when James visited, also reprints a more elaborate denial from the 1895 edition, citing a description of the house in Hawthorne’s 1837 story “Peter Goldthwaite’s Treasure” as textual evidence that Hawthorne used multiple sources for the Seven Gables. The 1902 Guide claims “the frame, so to speak, of the ‘House of the Seven Gables’ seems first to have been constructed” in this early story. Though the House of the Seven Gables may not be real, literary pilgrims will find other destinations in Salem to safely identify with Hawthorne’s texts. As the Guide graciously concludes, “there are . . . so many references in [The House of the Seven Gables] to real places . . . it is not surprising the mythical is mistaken for the real by unsuspecting readers” (10).Whether delusional, “useless,” or the folly of the “unsuspecting,” it is precisely the mistaking of the “mythical” for the “real” that makes the persistence of the nineteenth- and early twentieth-century search for an original House of the Seven Gables relevant today. These literary tourist practices are reading practices, as the continuous efforts to discipline and direct them indicate. The condemnations of the “useless search” for a tangible real are consistent with early endeavors to shape Hawthorne’s reception and train readers to read him as the great “Romancer.” What critics, canon-makers, and even guidebook writers do not seem to realize is that literary pilgrimages are a form of romance, a practice that performs on the streets of Salem the blending of the “actual” and the “ideal” advocated by Hawthorne on so many different occasions. Literary tours are extratextual extensions of practices applied first to (and inspired by) the texts themselves—and often they follow protocols advocated by the very critics irritated by the tour. The unsuspecting reader seems to correspond to the vulgar tourist condemned by more discerning, culturally differentiated, “picturesque travelers” of the same period. From this perspective, the literary tourist’s reading of a place is, at the same time, a reading of the literary text.We might argue, then, that the search for an auratic, original House of the Seven Gables, in which “the mythical is mistaken for the real,” is a most Hawthornean way of reading. When Henry James finds himself “wandering perhaps astray” (The American Scene 256) after arriving in Salem, the first thing he does is to ask directions to the House of the Seven Gables, just as less-discerning tourists had been doing for several decades. Though delayed, displaced, and perhaps evaded, the search for the Seven Gables structures James’s visit—and his narrative. Even when recounting other sites and time spent elsewhere, the search returns to interrupt the narrative: first to remind us that he is still approaching the House of the Seven Gables—“to which I am coming” (258)—and later to warn us that it will all turn out to be a “dreadful anticlimax” (259). Finally, before arriving at Turner Street, James engages in a back and forth about the status of the House pointed out by his guide, the “sympathetic American boy, who dropped straight from the hard sky” (260). Even within the labyrinthine Late style, James echoes the denials Lathrop and the Visitors’ Guide repeated for twenty-five years. As James memorably puts it, when his young guide suggests the house on Turner Street is the House of the Seven Gables, “I couldn’t take it in the least” (261).There are many reasons James “couldn’t take it.” But he differs, importantly, from Lathrop and the Visitors’ Guide, which argue repeatedly against the assertion of a single original of Hawthorne’s “visionary mansion.” James does not engage that question but instead rejects any association of these wood and stone realities with the house of ink and imagination. His rejection includes those who seek to encounter the “genius” of Hawthorne in situ or the original of the House of the Seven Gables.5 As James iterates at least six times in Hawthorne, written twenty-five years before his pilgrimage to Salem, “it cannot be too often repeated that Hawthorne was not a realist” (Hawthorne 124). This central tenet of James’s influential guide to reading Hawthorne in 1879 informs his reading of The House of the Seven Gables in 1904. To put too strict an emphasis on any house or any place as the source of the real is to invite readings of Hawthorne that James is unwilling to tolerate. If direct correspondences between the house of fiction and the house on Turner Street can be so readily (and firmly) established, then “unsuspecting” literary tourists and the purveyors of literary tourism may risk mistaking the great Romancer for something much closer to the realist writers of James’s generation.James need not be too worried, though. In practice, the poetics of literary tourism welcomes the ontological uncertainty of places that have what Washington Irving calls “storied and poetical associations” (12). Literary tourists may invite what James derides as “the poor illusion of a necessity of relation between the accomplished thing [the work of art] and those other quite equivocal things [the destinations of the tour]” (The American Scene 261). But many, or most, literary pilgrims understand the “quite equivocal” nature of the sites they visit. They do not insist on the “necessity” of a fixed relation between the actual and the imaginary; on the contrary, unfixing the boundaries is the point of the tour. The “equivocal” is part of the allure.Hawthorne anticipates and even instigates all of this with the amazingly acrobatic narrative devices that start The House of the Seven Gables. From the Preface to chapter 1 and beyond, Hawthorne deliberately kicks the “ladder . . . from the top of a wall,” to borrow the closing figure of James’s Salem tour, leaving readers and tourists to “[turn] a somersault into space” and “tread the air” (The American Scene 262). Hawthorne’s house, in this novel, is there and not there on the “soil of the County of Essex” (CE 2:3), conjured, denied, ultimately entered as the visitable house of fiction: a House of the Seven Gables in ink and wood and stone. By the time Hawthorne composed these acrobatics in The House of the Seven Gables, he was already an accomplished literary tour guide. “The Old Manse” and “The Custom-House” established him as a forerunner of a proto-auto-fiction that offers both guided topographical tours (of sites that become, in the act of writing, instant tourist destinations) and visits to the author as the object of the tour. Hawthorne’s many presentations of the scene of creative production invite more intimate access to the “genius” at work than any traditional pilgrimage to an author’s birthplace, the “author’s seat,” or any other literary sites in wood and stone.Hawthorne’s innovative introductory essays, and their invocation of imagined presence, follow a long line of earlier experiments in the poetics of tourism that reach back to the unpublished collection Hawthorne once called “The Itinerant Story-teller.”6 Several tales and sketches from the 1830s and 1840s enact a tour within the story, or frame the central story with an authorial persona serving as guide—often, as in The House of the Seven Gables, to a visitable house of fiction or to sites with “storied and poetical associations.” Other texts theorize the tour. “My Visit to Niagara” (1835) performs a masterful anatomy of picturesque aesthetics, whereas the meta-fictional tour of Salem in “Alice Doane’s Appeal” dramatizes the relation of storytelling, the Gothic, and history. The Gothic tale “The Lily’s Quest” (1839) was reprinted in The Picturesque Pocket Companion, and Visitors’ Guide, Through Mount Auburn, where it helped visitors blur distinctions between fiction and the tour. Several decades later, Hawthorne’s explicit tours of Salem—“A Rill from the Town-Pump,” “Foot-prints on the Sea-shore,” “Main Street”—were transformed into a list of attractions in the Visitors’ Guide to Salem with directions to the original sites. At these sites, the Guide informs us, “one can hardly make a more pleasant pilgrimage . . . than by spending a half-hour, book in hand, reading one of his beautiful sketches, upon the very spot where Hawthorne himself stood when the inspiration seized him to write it” (Hunt, Guide 141 [1892]).This passage points again to the unresolvable paradox in the structure of literary tourism: like the two versions of the House of Seven Gables—there and not there—the “very spot where Hawthorne himself stood” is real and unreal. Literary pilgrims may walk to Essex Street or to the birthplace or to Gallows Hill, but where exactly did Hawthorne stand when “inspiration seized him”? The same writers who deny a single original structure for The House of the Seven Gables are willing to suspend skepticism about the authenticity of the real when it concerns the “very spot” where genius transpires (or possibly could). They do so because the promise of intimate relation, of imagined proximity, at the scene of creation is central to the poetics of tourism. Just as readers wish to enter and feel present in the storyworld a narrative creates, literary pilgrims wish to enter the world of the making of that story. The real becomes a means of reaching deeper into the unreal; presence on the tour intensifies the sense of presence in the text.7As the collection of essays in this special issue show, this process works in reverse as well: the fictive can enhance, or story, the real. Later editions of the Visitors’ Guide to Salem illustrate the process by closing the chapter on Hawthorne with an extract of what it calls the “weird detached paragraphs” of “Alice Doane’s Appeal.” This early hybrid text, part fiction and part sketch, certainly warrants the Guide’s description. Weird it is—formally, thematically, historically. Less expected is the praise the Guide bestows on the tale for creating a “picture of early Salem [that] is truthful and interesting” (161 [1894]). Here, the weird and Gothic point, somehow, to the real Salem. Hawthorne’s experimental storytelling “on the very spot” also spurs the people of Salem to commemorate, at last, the tragic executions on Gallows Hill. “A duty,” the Guide reports in 1894, “which the Essex Institute seeks to perform in this year of the two hundredth anniversary of the great jail delivery, the one bright spot in the gloom of that epoch in our history” (161).Whether or not that duty was performed as Hawthorne’s story envisions, “Alice Doane’s Appeal” secures a new afterlife as an incitement to both literary tourism and civic activism. In citing Hawthorne’s weird text, moreover, the Guide seems to accept the blurring of distinctions between the real and the unreal, and the imagined and the historical, that it insists on in the case of the house on Turner Street. With this appearance in the Guide, “Alice Doane’s Appeal” joins other Hawthorne texts, including The House of the Seven Gables, that have been absorbed into the de-differentiating discourse of literary tourism. After Caroline Emmerton “restored” the House of the Seven Gables in 1910 and opened the museum to the public, the process seems to have been complete. The 1916 Visitors’ Guide to Salem opens with a “Brief Itinerary” that includes: “‘House of the Seven Gables’ (so called), 54 Turner street, built about 1669; a favorite haunt of Hawthorne; now restored, with six furnished rooms, a secret staircase, furniture, relics and a ‘cent shop.’ Admission 25c” (np). . . . “This collection of houses now forms one of the greatest attractions for the visitor to Salem” (Visitors’ Guide 60 [1916]).The unusual range of materials in this special issue—a public lecture, two articles on Hawthorne’s novel, and an interview with leaders of The House of the Seven Gables Museum—presents the results of a collaboration the Nathaniel Hawthorne Society started with the museum in the fall of 2023. Members of the Hawthorne Society had long discussed initiating some form of “public humanities” project to reach across the divide between academic Hawthorne scholars, lay readers, and the vibrant institutions where the public meets Hawthorne on the ground. “The House of the Seven Gables” (and “The Old Manse” in Concord) remain popular destinations for tourists, and the people who run those sites teach tens of thousands of visitors about Hawthorne each year and help grow and sustain his readership. We wanted to join them in that work and to foster new collaborations for the future.Our first project was to establish the Hawthorne Society Annual Lecture at “The House of the Seven Gables.” Each spring, we invite a Hawthorne scholar to present a free, public lecture in Salem. Our goal is to share current scholarship with a wider public in an accessible style. We were very fortunate that the esteemed Americanist Robert Levine agreed to give our second annual lecture, which we planned to coincide with the American Literature Association conference in Boston. To complement our effort to bring an accomplished scholar to the House of the Seven Gables, we invited leaders of the museum to join us at the ALA conference. Executive Director Dakota Russell and Curator of Collections Susan Baker joined our roundtable “The House of Seven Gables in Ink, Wood, and Stone.” In keeping with our goal of taking a new approach to Hawthorne and to The House of the Seven Gables, we were pleased to invite early-career scholars to participate on the roundtable. Two were students at the time: Luke Woodard was an MA candidate and a teacher at a private secondary school and Mitchell Edwards was a PhD candidate at Rutgers. The essays and interview that follow have been expanded from the talks presented on that occasion.The Hawthorne Society Annual lecture took place Sunday afternoon after the close of conference activities. Just as we hoped members of the public would attend the lecture, we wanted to get scholars from the ALA in Boston to the House of the Seven Gables in Salem. Fortunately, a commuter ferry opened recently, and we purchased a set of group tickets, making it possible for twenty scholars from all over the world to take the trip through Boston Harbor and up the coast to Salem. The lecture took place in the “Great Chamber” of the “Hooper Hathaway House” (c. 1682), which was relocated to the museum campus in 1911 to save it from demolition. For much of the twentieth century, the house hosted Settlement classes and literary tourists in the “six furnished rooms” with baths. We had arrived, finally, at the House of Seven Gables as advertised in the Visitors’ Guide to Salem!Robert Levine gave his talk to a standing-room-only audience of students, scholars, and museum staff.8 The text of Levine’s talk, “Haunted Houses: The House of the Seven Gables and Uncle Tom’s Cabin,” is presented in this issue of Nathaniel Hawthorne Review without significant change. It strikes a fine balance between accessibility for a general audience (deftly summarizing scenes from the two haunted houses) and making an important, revisionary argument about Hawthorne’s engagement with questions of race and slavery in The House of the Seven Gables. Levine shows how the numerous references to color, blood, and race in the novel complicate and undermine the notions of white, racial purity that underlay Colonel Pyncheon’s “genealogical ambition to perpetuate his supposedly white family.” Thus, the original house of Pyncheon is haunted by more than Maule’s curse. Levine’s lecture, informed by his forthcoming book on Stowe and Black America, closes with a review of some interesting biographical convergences between the authors of the two houses that should serve as a corrective for our partial accounts of Stowe’s anger with Hawthorne’s dedication of Our Old Home to Franklin Pierce (“that traitor”!). Levine points out that despite her earlier outrage, Stowe gave her daughter an elegantly bound edition of Hawthorne’s collected works in 1865.The two essays that follow Levine’s “Haunted Houses” move comfortably back and forth between elements of the House’s unstable ontological status that I have outlined in this introduction: Hawthorne’s fictional narrative, the House of the Seven Gables in ink, and the novel’s afterlife as The House of the Seven Gables Museum in wood and stone. They conduct close, formal analyses of the narrative structures Hawthorne builds in his “visionary house,” and, as a nimble literary tourist might do, they read the history of the house through the lens of—and as an interpretation of—Hawthorne’s novel. The unreal and the real are in full dialectical play in both essays. Crucially, each moves beyond the binary of ink and wood to consider the House of the Seven Gables in the world—as it figures in the history of novelistic technique and on the “soil of the County of Essex” (3) and in the history of American literary criticism. Together they present new perspectives on the House of the Seven Gables in ink, wood, and stone as it persists in the wider literary and physical worlds.Luke Woodard’s “Crossing Thresholds in The House of the Seven Gables: Hawthorne’s Narrative Architecture and the Encounter with History” (this issue) begins by directing our attention to the interventions of Hawthorne’s narrator and to Hawthorne’s narrative technique in The House of the Seven Gables. Woodard shows that the trope of the threshold, often considered in terms of characterization and theme, also represents Hawthorne’s work as a “narrative architect . . . who constructs a house of words . . . that will be inhabited by readers.” Hawthorne’s house of ink, in Woodard’s conception, contains the house of stone within the fictional storyworld. Woodard takes the manifest threshold crossings as a trope for the way Hawthorne persistently blurs the very distinctions he claims to maintain between the real and the imaginary and the past and the present. He argues that Hawthorne uses this liminal “narrative architecture” along with the scenes of storytelling inside The House of the Seven Gables to dramatize “the importance of form and style in facilitating an imaginative encounter with history.” In a final critical turn, Woodard looks ahead to Hawthorne’s influence on The House of the Seven Gables Museum as evidence that “Hawthorne’s narrative techniques have achieved physical expression . . . [in] a real structure.” The House of the Seven Gables in ink and wood crosses the threshold into the historical, contingent world.Mitchell Edwards’s “Flip This House: Caroline Emmerton’s Activist Hermeneutics and The House of the Seven Gables” takes this turn to the House of the Seven Gables in the world even further. He uses archival research, book history, and an original conception of activist literary criticism to historicize Caroline Emmerton’s work at the House of the Seven Gables and “flip” our understanding of her contributions. Edwards starts with the assertion that “the house and the book are two linked components of a composite cultural text” and argues that Emmerton’s renovations of the House also begin her renovation of Hawthorne’s novel, or, more precisely of the visitor-reader’s interpretation of the book. Edwards further shows that Emmerton’s varied activities, her essays, plays written for performance at the Settlement house, and republication of the “Visitors’ Edition” of the novel constitute a form of social activism and literary interpretation—what he calls an “activist hermeneutics.” Edwards reads Emmerton’s contribution to this emerging mode in the context of other twentieth-century activist literary movements and concludes with the bold claim that Emmerton is “invested in conscripting Hawthorne for radical social change, placing him at the center of a public humanities project marked by its Progressive Era origins.”Those origins continue to influence how visitors experience the House of the Seven Gables and to inform the larger work of the “House of the Seven Gables Settlement Association” (Emmerton’s original organization, which owns and operates the museum). We close this special issue with an edited transcript of an interview with our partners in our contemporary public humanities project: Executive Director Dakota Russell and Curator of Collections of the Seven Gables Susan Baker. Russell and Baker talk about the history of the House since Caroline Emmerton created the Settlement Association and opened the museum, about continuities with Emmerton’s mission in their settlement work and programming today, and about their representation of Hawthorne’s work and life at the Seven Gables. They also discuss their new initiative to revitalize the Hawthorne birthplace museum and to become a hub for Hawthorne studies and literary tourism. The Hawthorne Society has collaborated on this project from its inception, and we will continue as it goes forward. (You may hear more about fundraising efforts in the future.)We hope to see you in Salem for our next House of the Seven Gables lecture—and then again in June of 2028 for our next international Hawthorne Society conference!
Keywords: dept.eng

The House of the Seven Gables Then and Now: A Conversation with Executive Director Dakota Russell and Curator of Collections Susan Baker of The House of the Seven Gables Settlement Association (transcript from September 18, 2025) - Baraw, Charles; Russell, Dakota; Baker, Susan (Nathaniel Hawthorne Review, 2025)
ABSTRACT. A conversation with Dakota Russell, Executive Director, Susan Baker, Curator of Collections from The House of the Seven Gables Settlement Association, and Charles Baraw, past president of the Nathaniel Hawthorne Society.
Keywords: dept.eng

Thematic section on premodern digital ecologies - Malcolm, Aylin; Richmond, Andrew (Digital Scholarship in the Humanities, 2026)
Keywords: dept.eng

Property and precarisation: reading Seth Tobocman’s War in the Neighborhood and Fly’s CHRON!IC!RIOTS!PA!SM! - Stretch, Cynthia (Textual Practice, 2025)
Keywords: Fly (Elen Orr); Isabell Lorey; Property (philosophy); Reading (process); Seth Tobocman; bad debt; dept.eng; precarisation; squatting

“The broken schippus he ther fonde”: Shipwrecks and the Human Costs of Investment Capital in Middle English Romance - Richmond, Andrew M. (Neophilologus, 2015)
Featuring prominently in the romance imagination as terrifying obstacles in the hero’s path, shipwrecks are nevertheless often presented from the salvager’s perspective. Romances abound with knights, clerks, and merchants who obsessively observe nearby beaches and cautiously (yet excitedly) examine the contents of wrecked vessels. Washed ashore, such fruits of maritime disaster delineate medieval English conceptions of seashores as dangerous yet profitable spaces, wherein seaside harvests of (un)natural resources help to stimulate local economic networks. Designations of these shipwrecks as “magical” or “fortuitous” cannot, however, completely elide the source of such wealth in others’ suffering—an unavoidable implication that interrogates contemporary means of attaining investment capital. As such, this paper examines how the littoral space of the seashore is cast as a source of perilous and problematic material bounty in many Middle English romances.
Keywords: Emaré; Geoffrey Chaucer; John Gower; Middle English romance; Shipwrecks; Sir Amadace; dept.eng

Affect, Semiotics, Volition: Heteroregulation and Affectivating. - Larocco, Steve (I Activate You To Affect Me, 2018)
The second volume of Annals of Cultural Psychology is dedicated to the affective nature of human social relationships with the environment. The chapters here included explore the historical, theoretical and practical dimensions of the concept of affectivating originally introduced by one of us (Valsiner, 1999), as a potential tool of inquiry into the affective-sensitive dimension of psychological life within a cultural-psychological framework. The concept of affectivating involves two psychological dimensions often undervalued or even obliterated from contemporary cultural psychology, namely the affective involvement and the agentivity of people in their social encounters. Through several examples –‘feeling-at-home’, silence spaces and rituals, memorials, music and poetry, among others– we show individual’s concrete actions in mundane everyday life aim to give an affective personal sense to the world around. This focuses on the primary affective nature of human meaning construction that guides the person in one’s continuing feeling-into-the-world. At a theoretical level the notion of affectivation challenges contemporary Cultural Psychology to rescue subjectivity, not only symbolism. Affectivation propounds a return to the long, but partially forgotten, organismic tradition, represented in the history by thinkers like Wilhelm Dilthey, Jakob von Uexküll and Kurt Goldstein. Cultural psychology has to bring semiosis back to the vital background of human experience.

Normal: A Chaplain, a Community with HIV/AIDS, and the Eternal Life of Stories - Kerr, Audrey Elisa (Cascade Books, 2018)
This book chronicles the intersection of chaplaincy, autopathography (illness narratives), and stigmatized illness through the observations and stories of a chaplain working at a facility for people with HIV and AIDS. Trained as both an ethnographer and a chaplain, Audrey Elisa Kerr uses memoir to bridge the relationship between caregiver and patient, and allows stories of marginality to frame both her patients’ stories and her own.
Keywords: dept.eng

Dead Narratives: Defining Humanity through Stories - Ellis, Scott (The Apocalypse in Film: Dystopias, Disasters, and Other Visions about the End of the World, 2015)
We live in a world at risk. Dire predictions about our future or the demise of planet earth persist. Even fictional representations depict narratives of decay and the end of a commonly shared social reality. Along with recurring Hollywood blockbusters that imagine the end of the world, there has been a new wave of zombie features as well as independent films that offer various visions of the future. The Apocalypse in Film: Dystopias, Disasters, and Other Visions about the End of the World offers an overview of Armageddon in film from the silent era to the present. This collection of essays discusses how such films reflect social anxieties—ones that are linked to economic, ecological, and cultural factors. Featuring a broad spectrum of international scholars specializing in different historical genres and methodologies, these essays look at a number of films, including the silent classic The Four Horsemen of the Apocalypse, the black comedy Dr. Strangelove or: How I Learned to Stop Worrying and Love the Bomb, the Mayan calendar disaster epic, 2012, and in particular, Lars Von Trier’s Melancholia, the focus of several essays.As some filmmakers translate the anxiety about a changing global climate and geo-political relations into visions of the apocalypse, others articulate worries about the planet’s future by depicting chemical warfare, environmental disasters, or human made destruction. This book analyzes the emergence of apocalyptic and dystopic narratives and explores the political and social situations on which these films are based. Contributing to the dialogue on dystopic culture in war and peace, The Apocalypse in Film will be of interest to scholars in film and media studies, border studies, gender studies, sociology, and political science.

Making the Radical University: Identity and Politics on the American College Campus, 1966–1991 - Kalbfleisch, Elizabeth M. (University of Massachusetts Press, 2024)
In the 1960s, professors, students, and activists on the political Left viewed college curricula as useful sites for political transformation. They coordinated efforts to alter general education requirements at the college level to foster change in American thought, with greater openness toward people who had previously been excluded, including women, people of color, the poor and working classes, people with disabilities, and members of the LGBTQ community. Their work reshaped American culture and politics, while prompting a significant backlash from conservatives attempting to, in their view, protect classical education from modern encroachment. Elizabeth M. Kalbfleisch details how American universities became a battleground for identity politics from the 1960s through the 1980s. Focusing on two case studies at Stanford University and the University of Texas at Austin, Making the Radical University examines how curricular changes led to polarizing discussions nationwide around academic standards and identity politics, including the so-called canon wars. Today, these debates have only become more politically charged, complex, and barbed.
Keywords: dept.eng

Realism - Petrie, Paul R. (The Louisa May Alcott Encyclopedia, 2001)
Louisa May Alcott (1832-1888) is arguably the most widely read 19th-century author in America. Even through the 1990s, her books continued to appear on bestseller lists and her works were made into films. She has long been a staple of children's literature courses and now also receives significant attention in American studies and women's studies classes. While her tremendous popularity has yielded numerous biographies and a growing number of critical works, very few reference books have been devoted to Alcott studies and none are particularly current or complete. This book collects in a comprehensive and reliable single volume the most important facts about Alcott's life and works.This reference surveys the basic biographical details about Alcott's family and personal life. It supplies essential information on her historical and cultural contexts, including her place in the 19th century publishing milieu, various reform movements, and major historical events, such as the Civil War. It also treats her writings, both the adult and children's works, in an accurate, informative, and accessible manner. The volume includes more than 600 alphabetically arranged entries. Each entry discusses the topic's relevance to Alcott's life and current scholarship about her. Many of the entries close with brief bibliographies, and the book concludes with a list of works for further reading.
Google-Books-ID: sPMBb1Ql_9UC
Keywords: Literary Criticism / American / General; Literary Criticism / General

My Contraband (1863) - Petrie, Paul R. (The Louisa May Alcott Encyclopedia, 2001)
Louisa May Alcott (1832-1888) is arguably the most widely read 19th-century author in America. Even through the 1990s, her books continued to appear on bestseller lists and her works were made into films. She has long been a staple of children's literature courses and now also receives significant attention in American studies and women's studies classes. While her tremendous popularity has yielded numerous biographies and a growing number of critical works, very few reference books have been devoted to Alcott studies and none are particularly current or complete. This book collects in a comprehensive and reliable single volume the most important facts about Alcott's life and works.This reference surveys the basic biographical details about Alcott's family and personal life. It supplies essential information on her historical and cultural contexts, including her place in the 19th century publishing milieu, various reform movements, and major historical events, such as the Civil War. It also treats her writings, both the adult and children's works, in an accurate, informative, and accessible manner. The volume includes more than 600 alphabetically arranged entries. Each entry discusses the topic's relevance to Alcott's life and current scholarship about her. Many of the entries close with brief bibliographies, and the book concludes with a list of works for further reading.
Google-Books-ID: sPMBb1Ql_9UC
Keywords: Literary Criticism / American / General; Literary Criticism / General

James Family - Petrie, Paul R. (The Louisa May Alcott Encyclopedia, 2001)
Louisa May Alcott (1832-1888) is arguably the most widely read 19th-century author in America. Even through the 1990s, her books continued to appear on bestseller lists and her works were made into films. She has long been a staple of children's literature courses and now also receives significant attention in American studies and women's studies classes. While her tremendous popularity has yielded numerous biographies and a growing number of critical works, very few reference books have been devoted to Alcott studies and none are particularly current or complete. This book collects in a comprehensive and reliable single volume the most important facts about Alcott's life and works.This reference surveys the basic biographical details about Alcott's family and personal life. It supplies essential information on her historical and cultural contexts, including her place in the 19th century publishing milieu, various reform movements, and major historical events, such as the Civil War. It also treats her writings, both the adult and children's works, in an accurate, informative, and accessible manner. The volume includes more than 600 alphabetically arranged entries. Each entry discusses the topic's relevance to Alcott's life and current scholarship about her. Many of the entries close with brief bibliographies, and the book concludes with a list of works for further reading.
Google-Books-ID: sPMBb1Ql_9UC
Keywords: Literary Criticism / American / General; Literary Criticism / General

Henry Ward Beecher - Petrie, Paul R. (The Louisa May Alcott Encyclopedia, 2001)
Louisa May Alcott (1832-1888) is arguably the most widely read 19th-century author in America. Even through the 1990s, her books continued to appear on bestseller lists and her works were made into films. She has long been a staple of children's literature courses and now also receives significant attention in American studies and women's studies classes. While her tremendous popularity has yielded numerous biographies and a growing number of critical works, very few reference books have been devoted to Alcott studies and none are particularly current or complete. This book collects in a comprehensive and reliable single volume the most important facts about Alcott's life and works.This reference surveys the basic biographical details about Alcott's family and personal life. It supplies essential information on her historical and cultural contexts, including her place in the 19th century publishing milieu, various reform movements, and major historical events, such as the Civil War. It also treats her writings, both the adult and children's works, in an accurate, informative, and accessible manner. The volume includes more than 600 alphabetically arranged entries. Each entry discusses the topic's relevance to Alcott's life and current scholarship about her. Many of the entries close with brief bibliographies, and the book concludes with a list of works for further reading.
Google-Books-ID: sPMBb1Ql_9UC
Keywords: Literary Criticism / American / General; Literary Criticism / General

John Brown - Petrie, Paul R. (The Louisa May Alcott Encyclopedia, 2001)
Louisa May Alcott (1832-1888) is arguably the most widely read 19th-century author in America. Even through the 1990s, her books continued to appear on bestseller lists and her works were made into films. She has long been a staple of children's literature courses and now also receives significant attention in American studies and women's studies classes. While her tremendous popularity has yielded numerous biographies and a growing number of critical works, very few reference books have been devoted to Alcott studies and none are particularly current or complete. This book collects in a comprehensive and reliable single volume the most important facts about Alcott's life and works.This reference surveys the basic biographical details about Alcott's family and personal life. It supplies essential information on her historical and cultural contexts, including her place in the 19th century publishing milieu, various reform movements, and major historical events, such as the Civil War. It also treats her writings, both the adult and children's works, in an accurate, informative, and accessible manner. The volume includes more than 600 alphabetically arranged entries. Each entry discusses the topic's relevance to Alcott's life and current scholarship about her. Many of the entries close with brief bibliographies, and the book concludes with a list of works for further reading.
Google-Books-ID: sPMBb1Ql_9UC
Keywords: Literary Criticism / American / General; Literary Criticism / General

When I'm done helping with your battles, I've got work to do: Black feminism, white power, and the messy swelling of the margins - Kerr, Audrey E. (Our Voices Our Stories: An Anthology of Writings Advancing, Celebrating, Embracing and Empowering Girls and Women of Color, 2019)
"Our Voices Our Stories" is filled with thought-provoking poems, essays, short stories and other writings advancing, celebrating, embracing and empowering girls, teens and women of color worldwide. The diverse national and international voices represented in this anthology focus on the psychological, emotional, physical and social issues, traumas and challenges experienced by girls, teens and women of color. The writing will encourage society to understand what it means to be a girl, teen and woman of color living in a society that does not always listen to hear their voices or their stories.
Google-Books-ID: s9MEyAEACAAJ
Keywords: dept.eng

Christian identity, piety, and politics in early modern England - Dodson, J. Michael (Reformation, 2023)
Num Pages: 3
Keywords: book.review; dept.eng

Virginia Woolf, money, and “the world’s oldest profession” - Neverow, Vara (ITINERÁRIOS – Revista de Literatura, 2023)
Keywords: dept.eng

Black Women Speaking From Within - Hope, Kelly (Peter Lang, 2019)
In Black Women Speaking From Within: Essays and Experiences in Higher Education, contributors use intersectional and interdisciplinary lenses to share the ways in which they understand, navigate, resist, and transform student services, learning, teaching, and existing in the academy. This book explores and discusses the following question: How do Black women experience and perceive place and agency in higher education? Black Women Speaking From Within draws upon the influence organizational culture, sense-making, and sisterhood has on praxis and pedagogy and places the Black woman’s stories and experiences at the center of the conversation.
Keywords: dept.eng

Oh So Yum! Inspiring Others to Explore the Many Flavors of Plant-Based Nutrition with Everyday Favorites and Weekend Fun Food: Volume 1: Non-Dairy Edition - Gibson, Lori Angelica (White Dove Cottage Industries, LLC, 2023)
Oh So Yum! Volume 1 is a little bit gourmet and a little bit every day. With recipes for non-dairy cheeses, savory entrees, sweet treats and so much more, there is something to satisfy every craving and the most discriminating palates.Whether you're new to plant-based nutrition or a seasoned veteran, you can continue to enjoy your favorite flavors while benefitting animals, the planet and your health. This book will show you how and will quickly become your most reached for resource for quick and easy, tasty and satisfying, crowd-pleasing meals.Praise for Oh So Yum!“Oh So Yum is not just the title of this wonderful book. It is exactly what this book is about—creating delicious and surprisingly easy foods that have all the taste and none of the regrets that often accompany tasty meals. The instructions are simple, and the results are spectacular.” - Neal D. Barnard, MD, FACCAdjunct Professor, George Washington University School of MedicinePresident, Physicians Committee for Responsible Medicine“Anyone who thinks plant-based eating means sacrificing foods you love, this book will quickly change your mind! Written from a clear place of passion—Lori has created the ultimate introduction and delicious guide full of many classic dishes and favorite desserts, plus lots of staple recipes to keep stocked in your fridge and use a thousand different ways!”- Natalie ThomasRecipe and Video Creator, Feasting on Fruit“Lori’s Feta cheese is FANTASTIC!!! She could start up a business selling vegan cheeses. I bet there are a lot of people looking for good alternatives – this one is the best!- Dawn Duval, Area Supervisor“Wow! Lori’s aged blue cheese is delicious. I was going to let it sit in the cellar to age a bit longer but couldn’t resist trying it with some marinated eggplant!!! Thank you again!!!!!!”- Cindy Schrank Kane, Maven of Moderation“The ricotta recipe turned out great! Very easy. I usually make a cashew ricotta but will be replacing it with this recipe because this tastes a lot more like real ricotta to me. I bet I could swap this for dairy ricotta in any stuffed/layered pasta recipe without my non-veg friends and family noticing. I made the red pepper-fennel pasta with it too and liked how easy it was to transform the ricotta into a creamy pasta sauce.”- Melissa McBerkowitz, Recipe Testing Team, USA“The gelato is absolutely delicious! I took a portion to my mother who is vegetarian and trying to reduce her dairy intake and she said if she could buy vegan ice cream like this in the shops she would be very happy!”- Caroline Christian, Recipe Testing Team, UKWhat’s inside: 50+ whole food plant-based recipes including…Fresh, cultured and aged cheeses including feta, ricotta, mozzarella and cream cheese, plus REAL aged cheeses such as Camembert and Blue cheese.Veganized versions of popular dishes including stuffed shells, spanakopita (Greek Spinach Pie) and zucchini pad Thai.Dressings, sauces, appetizers and sides such as gourmet blue cheese dressing, marinated feta, mushroom antipasto, marinated eggplant and even potato salad.Weekend fun foods including smoked portobello CrunchWrap, jackfruit caritas and pizzeria style pizza.Fabulous desserts such as cheesecake, cashew cream parfaits, chocolate peanut butter pie and gelato.
Keywords: dept.eng

"A Charnel House of Uncertainty, Doubt, and Error": Medical and Narrative Authority in Some Fin-de-Siècle Fictions - Fluhr, Nicole (Literature and Medicine, 2021)
0 citations (Crossref) [2023-10-31]
Keywords: dept.eng; peer-reviewed

“Maybe There’s Nobody to Shoot”: The Disappearing Landlord in 20th-Century U.S. Fiction - Stretch, Cynthia (American Houses: Literary Spaces of Resistance and Desire, 2022)
Section: American Houses: Literary Spaces of Resistance and Desire
Keywords: American Studies; General; History; North America; Social Sciences; dept.eng

At Home on the Stage: Toward an Affective Geography of Gentrification and Eviction in U.S. Cities - Stretch, Cynthia (Literary Representations of Precarious Work, 1840 to the Present, 2021)
Spoken word performance addressing gentrification and eviction encodes and embodies increasingly abstract and bureaucratically obfuscated processes of racialized dispossession in U.S. cities. Developing tropes across three works about housing precarity are read as poets’ attempts to identify the antagonists behind the digital wall of finance capital. Whereas the interactions of housing-insecure people with and within the housing market generate socially devalued identities, spoken word’s emphasis on “authenticity” requires poets to stand up as and for themselves as they wish to be (seen). In so doing, poets attempt to connect with audiences in real time to locate or reconstitute a stance as agents, however provisionally.
Keywords: A Scribe Called Quess?; Eviction; Gentrification; Nick Petrie; Roya Marsh; Spoken word poetry; dept.eng

War in Travel Literature - Dubino, Jeanne; Kocabıyık, Orkun; Marino, Elisabetta; Smyth, Andrew J. (Cambridge Scholars Publishing, 2023)
These twelve chapters show how war functions as a subject, theme, impetus–willing and not–and backdrop in travel writing. Literature about travel and war in tandem enables readers to rethink both categories. The forms of travel writing about war addressed in this collection, including cookbooks and military magazines along with nonfiction narrative and memoir, reveal how heterogenous travel writing can be. To study travel in connection with war expands readers' understanding of the multiple motivations instigating travellers' journeys. War is about more than fighting on a battlefield; its reach is extensive, encompassing the spheres surrounding its battlefields and fronts. The many actors involved in any conflict attests to the ways war is absorbed into their worlds, permeates their thoughts and spurs their actions. Readers interested in travel literature from the beginning of the nineteenth century through the present day will find this volume to be of especial interest.
Google-Books-ID: uYLxzwEACAAJ
Keywords: dept.eng

Facing the Other: Responsibility, Convictions and the Ethics of Attachment - Larocco, Steve (The Ethos of Theorizing: Peer-reviewed, Edited and Selected Proceedings of the Seventeenth Biennial Conference of International Society for Theoretical Psychology, Tokyo, Japan, August 2017, 2019)
Google-Books-ID: sQUeyQEACAAJ
Keywords: dept.eng; peer-reviewed

Chronic: A Memoir - Dimyan, Rebecca (Woodhall Press, 2023)
In this powerful debut, Rebecca Dimyan details her experience with endometriosis, a chronic disease which effects one in ten women worldwide. This painful condition takes an average of seven years to be diagnosed and has no proven cure. Most women will undergo multiple surgeries, take countless painkillers and other drugs, and will still endure regular pain and other complications. With honesty, vulnerability, and sometimes humor, Dimyan explores the ways the condition has impacted her experiences, her body, her pain, and her joy. She takes her audience on an emotional journey through her teenage years, early twenties, and into her thirties as she becomes a professional woman, wife, and mother. Dimyan blends research, anecdotes, and advice as she shares the relief she’s found through alternative treatments and holistic medicine. Chronic isn’t just a story about one woman’s illness—it is a memoir about all the pain, pleasure, heartbreak, friendship, love, and hope she experiences on her path to healing.
Keywords: dept.eng

Lessons for My Daughters (Taught to Me by bell) - Hutchinson, Brandon L. A. (Navigating Academia During COVID-19: Perspectives and Strategies from BIPOC Women, 2023)
As a tenured professor at a predominantly white institution (PWI), I am aware of the hardships we face in the academy; as a mother of three Black girls, a wife to a Black man, I am full. And yet, I must make space to see my own self clearly. Each day as a Black woman, I must set the intention to save my own life.
Keywords: Identity; Introspection; Self-care; dept.eng

My Face-Eating Octopus - Furey, Rachel (Harpur Palate, 2023)
Keywords: dept.eng; literary-nonfiction

Sabbatical Leave Report - Hochman, Will (Distribution: fall-spring-15 ; English., 2015)
From the report: "My goal was to develop, reserach and write my next study on J.D. Salinger. With the aid of research and [sic] on Salinger's letters at the Morgan Library and The Firestone Library (Princeton), and several visits to his Cornish home, I was able to finish one manuscript, begin another, and start a Salinger essay designed to attract interest in my manuscript. I am happy to report that I completed my next manuscript, Harvesting Salinger's Rye, because I earned the tremendous good fortune to recieve support from SCSU."
Keywords: dept.eng; faculty_collection; sabbatical_report

Breathing, One Adult. - Troy, Robin (2012)
Completed 200 pages of a book documenting surviving Hodgkins Lymphoma, a family history describing the experiences both of the author and of her mother.
Keywords: dept.eng; faculty_collection; sabbatical_report

Virginia Woolf's Jacob's Room: An Introduction and Annotations. - Neverow, Vara (2007)
Keywords: dept.eng; faculty_collection; sabbatical_report

American Pantheon: Poems. - Mock, Jeff (2005)
Keywords: dept.eng; faculty_collection; sabbatical_report

Poetic Healing of the Collective Black Mind: The Example of Langston Hughes and Maya Angelou. - Ogbaa, Kalu (2003)
Keywords: dept.eng; faculty_collection; sabbatical_report

Seven Holy Women Among the Desert Fathers in the First English Edition of Vitas Patrum. - Holbrook, Sue Ellen (Spring;English., 2002)
Keywords: dept.eng; faculty_collection; sabbatical_report

The Jumper. - Parrish, Tim (2002)
Keywords: dept.eng; faculty_collection; sabbatical_report

[A Book on Blake] - Rosso, G. Anthony (2002)
Keywords: dept.eng; faculty_collection; sabbatical_report

Robert Blake: His Watercolors and His Poetry. - Rosso, Tony (fall : English., 2002)
Keywords: dept.eng; faculty_collection; sabbatical_report

The Gendered Revolution in Writing: The Story of the First Prose Masterpiece in Western Civilization. - Blackmer, Corinne (2000)
Keywords: dept.eng; faculty_collection; sabbatical_report

Critical Companion to J.D. Salinger: A Literary Reference to His Life and Work - Mueller, Bruce F.; Hochman, Will (Facts On File, 2011)
Keywords: Handbooks; manuals; etc; Salinger; J. D. (Jerome David); 1919-2010; dept.eng; faculty_collection

The Life and Times of Chinua Achebe - Ogbaa, Kalu (Routledge, Taylor & Francis Group, 2022)
"The Life and Times of Chinua Achebe introduces readers to the life, literary works, and times of arguably the most widely-read African novelist of recent times, an icon, both in continental Africa and abroad. The book weaves together the story of Chinua Achebe, a young Igboman whose novel Things Fall Apart opened the eyes of the world to a more realistic image of Africa, a continent warped by generations of European travelers, colonists, and writers. Whilst continuing to write further influential novels and essays, Achebe also taught other African writers to use their skills to help their national leaders to fight for their freedoms in the post-colonial era, as internal warfare compounded the damage caused by European powers during the colonial era. In this book Kalu Ogbaa, an esteemed expert on Achebe and his works, draws on extensive research and personal interviews with the great man and his colleagues and friends, to tell the story of Achebe and his work. This intimate and powerful new biography will be essential reading for students and scholars of Chinua Achebe, and to anyone with an interest in the literature and post-colonial politics of Africa"–
Keywords: 20th century; Achebe; Chinua; Achebe; Chinua; Biography; Political and social views; Authors; Nigerian; dept.eng; faculty_collection

Poisoning the Wells: Antisemitism in Contemporary America - Pessin, Andrew; Blackmer, Corinne E. (ISGAP, 2021)
Keywords: Antisemitism; United States; dept.eng; faculty_collection

The Number 43: The Life and Legacy of Wild Bill Greco - Greco, Sarah (Coastal 181, 2018)
Keywords: Stock car racing; United States; United States; Stock car drivers; dept.eng

After Hours: Poems - Mottola, Pat (Five Oaks Press, 2018)
Keywords: dept.eng

Sabbatical project: a Norton critical edition of W. D. Howell's novel, The rise of Silas Lapham (1885) - Petrie, Paul R. (2017)
Keywords: dept.eng; faculty_collection; sabbatical_report

Sabbatical Leave Report Spring 2016: In Search of Mercy Ethnicity, Gender and Parochial Education in Washington Height, New York, and the Catechism of Bella Abzug and Audre Lorde - Kerr, Audrey Elisa (2016)
The purpose of this essay was to expand the ways critics think about Harlem and the Heights following the Great Depression by recovering women's creative responses to social and political angst in predominantly Catholic spaces.
Keywords: dept.eng; faculty_collection; sabbatical_report

Under the Red Dress - Mottola, Pat (Five Oaks Press, 2016)
Keywords: American poetry; dept.eng; faculty_collection

The Religion of Empire: Political Theology in Blake's Prophetic Symbolism - Rosso, G. A. (The Ohio State University Press, 2016)
The Religion of Empire: Political Theology in Blake's Prophetic Symbolism is the first full-length study devoted to interpreting Blake's three long poems, showing the ways in which the Bible, myth, and politics merge in his prophetic symbolism. In this book, G. A. Rosso examines the themes of empire and religion through the lens of one of Blake's most distinctive and puzzling images, Rahab, a figure that anchors an account of the development of Blake's political theology in the latter half of his career. Through the Rahab figure, Rosso argues, Blake interweaves the histories of religion and empire in a wide-ranging attack on the conceptual bases of British globalism in the long eighteenth century. This approach reveals the vast potential that the question of religion offers to a reconsideration of Blake's attitude to empire. The Religion of Empire also reevaluates Blake's relationship with Milton, whose influence Blake both affirms and contests in a unique appropriation of Milton's prophetic legacy. In this context, Rosso challenges recent views of Blake as complicit with the nationalism and sexism of his time, expanding the religion-empire nexus to include Blake's esoteric understanding of gender. Foregrounding the role of female characters in the longer prophecies, Rosso discloses the variegated and progressive nature of Blake's apocalyptic humanism.
SCSU Faculty Scholar Award
Keywords: Blake; William; 1757-1827; Criticism and interpretation; Blake; William; 1757-1827; History and criticism; Prophecies in literature; Political and social views; Blake; William; 1757-1827. Four Zoas; Blake; William; 1757-1827. Milton; Blake; William; 1757-1827. Jerusalem; Political theology; Epic poetry; English; Religion; Blake; William; 1757-1827; SCSU Faculty Scholar Award; award_winner; dept.eng

American Woman Suffrage Postcards: A Study and Catalog - Florey, Kenneth (McFarland & Company, Inc., Publishers, 2015)
"American women's suffrage activists were fascinated with suffrage themed postcards. They collected them, exchanged them, wrote about them, used them as fundraisers and organized 'postcard day' campaigns. The cards they produced were imaginative and ideological, advancing arguments for the enfranchisement of women and responding to antisuffrage broadsides. Publishers were also interested in suffrage cards, recognizing their profit potential"–
Keywords: Catalogs; Catalogs; Postcards; History; History; Postcards; Pictorial works; Pictorial works; Women; Political aspects; Suffrage; United States; Women; dept.eng; faculty_collection

Perennial - Shipley, Vivian (Negative Capability Press, 2015)
Keywords: dept.eng; faculty_collection

The Poet - Shipley, Vivian (Louisiana Literature Pres, 2015)
Keywords: dept.eng; faculty_collection

Sabbatical leave report: academic year 2014-15 - Hochman, Will (2014)
Hochman met his goal to develop, research and write a new study on J.D. Salinger. The manuscript "Harvesting Salinger's Rye" was completed and has been submitted to various publishers. He also engaged in non-Salinger scholarship delivering conference papers on creative writing. Hochman also used the sabbatical time to make improvements in his teaching and course content and to engage in professional reading.
Keywords: dept.eng; faculty_collection; sabbatical_report

Fall 2014 Sabbatical Leave Report - Johnson, Brian (2014)
Leave employed to complete draft of full manuscript of new poetry collection, now entitled About to Say.
Keywords: dept.eng; faculty_collection; sabbatical_report

Blinding Light - Beck, Christine (Grayson Books, 2013)
Keywords: dept.eng; faculty_collection

Women's Suffrage Memorabilia: An Illustrated Historical Study - Florey, Kenneth (McFarland & Company, Inc., 2013)
"This work analyzes 70 different categories of suffrage memorabilia, while providing numerous images of relevant objects along the way, and discusses these innovative production methods. Most important, this study looks at period accounts, often fascinating, of how, why, when, and where the memorabilia were used in both America and England"–
Keywords: Collectibles; Women; Great Britain; Suffrage; United States; Women; Women; dept.eng; faculty_collection

Carrying My Father's Torch: A Memoir - Ogbaa, Kalu (Carolina Academic Press, 2013)
Keywords: 1960-; Biography; College teachers; Biography; Fathers and sons; Biography; Igbo (African people); Biography; Immigrants; Biography; Nigeria; Civil War; 1967-1970; Connecticut; Family; Nigerian Americans; History; New Haven; Nigeria; Christian biography; Nigeria; Nigeria; Ogbaa; Kalu; Ogbaa; Kalu; United States; dept.eng; faculty_collection

Fear and What Follows: The Violent Education of a Christian Racist, a Memoir - Parrish, Tim (University Press of Mississippi, 2013)
An account of the author's spiral into racist violence during the latter years of desegregation in the 1960s and 1970s Baton Rouge.
Keywords: Baton Rouge; Baton Rouge (La.); Baton Rouge; Racism; Biography; Homes and haunts; Louisiana; Parrish; Tim; Authors; American; Race relations; dept.eng; faculty_collection

The Jumper - Parrish, Tim (Texas Review Press, 2013)
"Set amidst North Baton Rouge's inferno of industries and refineries, smack in the middle of low-rent crime and violence, The jumper is a fast-paced and gritty tale about characters who'd intimidate the thugs of a 1930s hard-boiled novel. Parrish's visceral yet lyrical prose, his structuring of fictional time, and his clear moral vision transform these tough-guy elements into an experience somehow luminescent, emotionally disturbing, and completely uplifting."–Back cover.
Keywords: Fiction; Young men; dept.eng; faculty_collection

Civil Twilight: Poems - Schilpp, Margot (Carnegie Mellon University Press, 2012)
Mad River Literary Festival Collection
Keywords: 21st century; American poetry; dept.eng; faculty_collection

The Networks of New Haven Culture, 1800-1850. - Ellis, Scott (2011)
Sabbatical research investigating the literary culture of New Haven, Connecticut, during the first half of the 19th century, encompasing book importers, booksellers, publishers, newspapers, periodicals, libraries, and literary societies. Based on extensive local collections dispersed throughout local repositories.
Keywords: dept.eng; faculty_collection; sabbatical_report

Liberty Lanes - Troy, Robin (University of Nevada Press, 2011)
Nelson Moore, one of the bowlers at Liberty Lanes, has recently become a hero by saving a teammate from choking on a chicken bone. Now he must deal with his sudden fame while coping with the early stages of dementia.–(Source of description unspecified.)
Keywords: Age groups; Aged; Aging people; Alleys; Bowling; Aphrenia; Aphronesia; Athletes; Athymia; Bowlers Fiction.; Bowlers.; Bowling alleys Montana.; Bowling lanes; Brain Diseases; Dementia.; Dementias; Država Montana; Elderly people; Electronic books.; Fiction.; Gerontocracy; Gerontology; Lanes; Bowling; MT; Monekana; Montana Eyaleti; Montana Fiction.; Montana Territory; Montana-sh; Montana.; Montanash; Montano; Neurobehavioral disorders; Old age; Old people; Older adults; Older people Fiction.; Older people.; Older persons; Persons; Politeia tēs Montana; Psychoses; Senior citizens; Seniors (Older people); Shtat Montana; Sports facilities; State of Montana; Statul Montana; Stories; Tales; dept.eng; faculty_collection; nne Aged

An Imperative Duty - Howells, William Dean (Broadview Press, 2010)
Keywords: Fiction; Fiction; Passing (Identity); Fiction; Young women; Racially mixed people; dept.eng; faculty_collection

Ruthless: Poems - Mock, Jeff (Three Candles Press, 2010)
Keywords: dept.eng; faculty_collection

Blood and Bravery: Voices of Biafran Veterans of the Nigeria-Biafra War - Ogbaa, Kalu (Sungai, 2010)
Keywords: Civil War; 1967-1970; History; Nigeria; dept.eng; faculty_collection

All of Your Messages Have Been Erased - Shipley, Vivian (Louisiana Literature Press, 2010)
Keywords: dept.eng; faculty_collection

Fall 2009 Sabbatical Leave Follow-Up Report - McEachern, Robert (2009)
I was awarded sabbatical leave for Fall 2009. My sabbatical proposal was titled “How Web 2.0 Technologies Are Transforming Writing in Nonprofit Organizations.” My plan, as laid out in my sabbatical proposal, involved tracking and analyzing the online presence of 3-5 nonprofit organizations, and reporting on the ways the nature of their organizational writing had changed, directly and indirectly, as a result of the use of web 2.0 technologies, including blogs, wikis, and social networking sites such as Facebook and Twitter.
Keywords: dept.eng; faculty_collection; sabbatical_report

Bear Country - Sonnenschein, Dana (NFSPS, 2009)
Keywords: Bears; Poetry; dept.eng; faculty_collection

Torch Lake & Other Poems - Johnson, Brian (Del Sol Press, 2008)
SCSU Faculty Scholar Award
Keywords: 21st century; 21st century; American poetry; Prose poems; American; American poetry; SCSU Faculty Scholar Award; award_winner; dept.eng; faculty_collection

Grace Cavalieri Interviews Vivian Shipley - Cavalieri, Grace; Shipley, Vivian (2007)
SCSU Faculty Scholar Award
Keywords: 21st century; 21st century; Poets; American; American poetry; Interviews; award_winner; dept.eng; faculty_collection

General Ojukwu: The Legend of Biafra - Ogbaa, Kalu (Triatlantic, 2007)
Keywords: 1960-1975; Africa; Africa; Biography; Biography; Nigeria; Biography; Statesmen; Ojukwu; Chukwuemeka Odumegwu; 1933-2011; Politicians; Politics and government; dept.eng; faculty_collection

Freer - Hochman, Will (Pecan Grove Press, 2006)
Keywords: dept.eng; faculty_collection

Natural Forms: Poems - Sonnenschein, Dana (Word Press, 2006)
Keywords: Nature; Poetry; dept.eng; faculty_collection

Conscience and Purpose: Fiction and Social Consciousness in Howells, Jewett, Chesnutt, and Cather - Petrie, Paul R. (University of Alabama Press, 2005)
"In a series of influential essays that appeared in Harper's, W.D. Howells argued for literature as a vehicle for social change. Literature could and should, Howells suggested, mediate across divisions of class and region, fostering cross-cultural sympathies that would lead to comprehensive social and ethical reform." "Paul R. Petrie explores the legacy of Howells's beliefs as they manifest themselves in his fiction and in the works of three major American writers - Charles W. Chesnutt, Sarah Orne Jewett, and Willa Cather. Each author struggled to adapt Howells's social-ethical agenda for literature to his or her own aesthetic goals and to alternative conceptions of literary purpose. Jewett not only embraced Howell's sense of social mission but also extended it by documenting commonplace cultural realities in a language and vision that was spiritual and transcendent. Chesnutt sought to improve relations between Anglo readers and African Americans, but his work, such as The Conjure Woman, also questions literature's ability to repair those divides." "Finally, Petrie shows how Cather, as she shifted from journalism to fiction writing, freed herself from Howells's influence. Alexander's Bridge (1912) and O Pioneers! (1913) both make reference to social and material realities but only as groundwork for character portrayals that are mythic and heroic. The result of Petrie's exploration is a refreshing reassessment of Howell's legacy and its impact on American literature and social history at the turn of the century."–Jacket.
SCSU Faculty Scholar Award
Keywords: Chesnutt; Charles W. (Charles Waddell); 1858-1932; Ethics; American fiction; Ethics; Cather; Willa; 1873-1947; Ethics; Howells; William Dean; 1837-1920; Ethics; Jewett; Sarah Orne; 1849-1909; History and criticism; Ethics in literature; Literature and society; SCSU Faculty Scholar Award; United States; Social ethics in literature; Conscience in literature; award_winner; dept.eng; faculty_collection

Laws of My Nature: Poems - Schilpp, Margot (Carnegie Mellon University Press, 2005)
Keywords: American poetry; dept.eng; faculty_collection

Hardboot: Poems New & Old - Shipley, Vivian (Louisiana Literature Press, Southeastern Louisiana University, 2005)
Keywords: Poets; American; dept.eng; faculty_collection

Caduceus: Poets at Art Place V.3 - Shipley, Vivian; Fusco, Tony; Yale University School of Medicine Yale Medical Group Art Place; Yale Medical Group (Yale Medical Group Art Place, 2005)
Poetry included in the partial contents note is composed of contributions from the faculty, staff, students and alumni of Southern Connecticut State University.
Keywords: Connecticut; Literature and science; New Haven; Literature and science; Poetry; Poetry; United States; United States; New Haven (Conn.); dept.eng; faculty_collection

No Angels but These - Sonnenschein, Dana (Main Street Rag, 2005)
Keywords: dept.eng; faculty_collection

The Nigerian Americans - Ogbaa, Kalu (Greenwood Press, 2003)
Keywords: Nigerian Americans; Immigrants; Social conditions; United States; Nigerian Americans; dept.eng; faculty_collection

Gleanings: Old Poems, New Poems - Shipley, Vivian (Louisiana Literature Press, 2003)
SCSU Faculty Scholar Award
Keywords: award_winner; dept.eng; faculty_collection

Corvus: Poems - Sonnenschein, Dana (Wind, 2003)
Fisher-Wirth, Ann W. Trinket poems.
Keywords: Corvus; Poetry; dept.eng; faculty_collection

Letters to J.D. Salinger - Kubica, Chris; Hochman, Will (University of Wisconsin Press, 2002)
"He published his only novel more than fifty years ago. He has hardly been seen or heard from since 1965. Most writers fitting such a description are long forgotten, but if the novel is The Catcher in the Rye and the writer is J.D. Salinger ... well, he's the stuff of legends, the most famously reclusive writer of the twentieth century. If you could write to him, what would you say?" "Salinger continues to maintain his silence, but Holden Caulfield, Franny and Zooey, and Seymour Glass - the unforgettable characters of his novel and short stories - continue to speak to generations of readers and writers. Letters to J.D. Salinger includes more than eighty personal letters addressed to Salinger from well-known writers, editors, critics, journalists, and other luminaries, as well as from students, teachers, and readers around the world, some of whom have just discovered Salinger for the first time. Their voices testify to the lasting impression Salinger's ideas and emotions have made on so many diverse lives."–Jacket.
Keywords: Correspondence; Authors and readers; Salinger; J. D. (Jerome David); 1919-2010; United States; Authorship; dept.eng; faculty_collection

A Century of Nigerian Literature: A Select Bibliography - Ogbaa, Kalu (Africa World Press, 2002)
Keywords: Bibliography; Nigerian literature; dept.eng; faculty_collection

When There Is No Shore - Shipley, Vivian (Word Press, 2002)
Keywords: Kentucky; Poetry; dept.eng; faculty_collection

Walking Blues: Making Americans from Emerson to Elvis - Parrish, Timothy (University of Massachusetts Press, 2001)
"Shows how our American social, racial, and ethnic conflicts often mark the starting point for the various acts of creation through which we make and remake ourselves as Americans."–Cover.
SCSU Faculty Scholar Award
Keywords: Civilization; Intellectual life; National characteristics; American; Cultural pluralism; Parrish; Philosophy; Blues (Music); Philosophy; United States; Social aspects; United States; United States; Popular culture; United States; Pragmatism; United States; award_winner; dept.eng; faculty_collection

Poetry Does Theology: Chaucer, Grosseteste, and the Pearl-Poet - Rhodes, James Francis (University of Notre Dame Press, 2001)
SCSU Faculty Scholar Award
Keywords: Criticism and interpretation; Langland; William; 1330?-1400? Piers Plowman; Chaucer; Geoffrey; -1400. Canterbury tales; Christian poetry; English (Middle); England; Grosseteste; Robert; 1175?-1253; History; History and criticism; Theology; History and criticism; Theology in literature; English poetry; Middle Ages; 600-1500; Patience (Middle English poem); Purity (Middle English poem); Pearl (Middle English poem); Middle English; 1100-1500; award_winner; dept.eng; faculty_collection

The World's Last Night: Poems - Schilpp, Margot (Carnegie Mellon University Press, 2001)
Keywords: American poetry; Women authors; dept.eng; faculty_collection

Down of Hawk: Poems - Shipley, Vivian (Sow's Ear Press, 2001)
Keywords: dept.eng; faculty_collection

Fishing Poems. - Shipley, Vivian (Pudding House Publications, 2001)
Keywords: dept.eng; faculty_collection

Panhandler: Special Issue: Photo/Text. - Shipley, Vivian (English Dept. of the University of West Florida, 2001)
Keywords: 20th century; Literature; Modern; dept.eng; faculty_collection

Self-Portrait - Johnson, Brian (Quale Press, 2000)
Keywords: dept.eng; faculty_collection

Red Stick Men: Stories - Parrish, Tim (University Press of Mississippi, 2000)
The characters in these stories "are always on the verge of disasters that emanate from the hard living they endure in the city they call 'Red Stick,'" i.e., Baton Rouge, Louisiana.–Jacket.
Keywords: Baton Rouge; Fiction; Fiction; Baton Rouge (La.); Louisiana; Oil industry workers; Social life and customs; dept.eng; faculty_collection

Fair Haven - Shipley, Vivian (Negative Capability Press, 2000)
Keywords: dept.eng; faculty_collection

Should we teach students how to bullshit? - McEachern, Peter J.; McEachern, Robert W. (Writing and Pedagogy, 2022)
Bullshit, as defined by Frankfurt (2005, p. 10), is language that is “disconnected from a concern for the truth.” Much scholarship shows that bullshit is a prominent feature in organizations that is difficult, if not impossible, to get rid of (e.g., McCarthy et al., 2020; Penny, 2010). Bullshit, by definition and by cultural practice, seems antithetical to business writing orthodoxy. As Thill and Bovée (2020) suggest in a representative textbook, communication should be clear and ethical. However, Spicer (2020) codifies bullshit as a social practice whose outcomes are not always dire. Well-crafted bullshit benefits its users, allowing them to “fit into a speech community, get things done in day-to-day interaction and bolster their image and identity” (Spicer, 2020, p. 20). Contrasting with business writing’s abstinence-only bullshit stance, this suggests that successful writers must adapt to their organization’s speech act practices. In this article, we argue that students must be taught about bullshit. After describing bullshit and its role in organizations, we show how business writing could incorporate a critically informed approach to bullshit in undergraduate courses, internship preparation courses, and other curricular instances in which students work directly with organizations. While bullshitting should not be outright encouraged, continued ignorance will do nothing to solve its associated problems. Promoting bullshit literacy, however, could both minimize bullshit’s harms and maximize its benefits. We close by describing how this approach could foster critical thinking skills, promote more seamless adaptation to organizational cultures and communication practices, and perhaps even improve mental health outcomes.
1 citations (Crossref) [2023-10-31]
Keywords: Bullshit; Bullshitology; Business Writing; dept.eng; peer-reviewed

We Need to Talk About War Metaphors in Oncology - McEachern, Robert W. (JCO Oncology Practice, 2022)
0 citations (Crossref) [2023-10-31]
Keywords: dept.eng

Tea Ceremony - Sonnenschein, Dana (Corvid Queen, 2022)
Water the color of oolong reflects her shape vanishing.
Keywords: dept.eng; ⛔ No DOI found

Nest Robbers - Sonnenschein, Dana (The Curator, 2022)
...
Keywords: dept.eng

Queering Anti-Zionism: Academic Freedom, LGBTQ Intellectuals, and Israel/Palestine Campus Activism - Blackmer, Corinne E. (Wayne State University Press, 2022)
"This book explores the work of five influential pro-BDS (Boycott, Divestment, and Sanctions) queer academic activists-Sarah Schulman, Jasbir Puar, Angela Davis, Dean Spade, and Judith Butler-each of whom exemplify different ideological and critical practices around anti-Zionism"–
Keywords: Boycotts; Foreign public opinion; Israel; Boycott; divestment; and sanctions movement; Zionism; Gay rights; Israel; Israel; Disinvestment; Politics and government; dept.eng; faculty_collection

Bird Guides (poem) - Sonnenschein, Dana (Thimble Literary Magazine, 2022)
Keywords: dept.eng

Lady Macbeth, her book - Sonnenschein, Dana (Embark: A Literary Journal for Novelists, 2022)
A.D. 1034 The king and queen took hawks out that day, and their retinue trailed along hills and swales, watching as Duncan and then Suthen lifted gauntleted arms and opened their fists. The hunting…
Keywords: dept.eng; ⛔ No DOI found

The misunderstood discipline of composition studies [3] - Hood, C.L. (Chronicle of Higher Education, 2003)
Keywords: dept.eng; ⛔ No DOI found

Illusions of a public, locations of conflict: Feeling like populace in William Dean Howells' A Hazard of New Fortunes - Stretch, C. (American Literary Realism, 2003)
Keywords: dept.eng; ⛔ No DOI found

Spectacle at the disco: Boogie nights, soundtrack, and the New American musical - Ritter, K. (Journal of Popular Film and Television, 2001)
In our postmodern visual culture, the idea of spectacle conjures images of excess. In defining spectatorship, we emphasize the visual, drawing physical eyewitnesses toward the spectacular moment itself and into the reification of that moment on the film screen. However, recent Hollywood cinema has challenged the notion that all spectacle must take place within the realm of the visual, as many films strive to reach spectators aurally, via their soundtracks. In particular, popular song has been used in many commercially successful films to re-create each spectator's relationship with his or her past. Films with best-selling pop soundtracks, such as The Wedding Singer and Romy and Michelle's High School Reunion, among others, have financially exploited the spectator's attention to familiar song within comedic narratives, prompting viewers to purchase collections of songs they may already own, motivated by nostalgia and pleasant rearrangements of these songs within light, entertaining narratives. In other cases, “retro” films such as 54 and The Last Days of Disco have attempted to capitalize on the popularity of musical trends, such as disco, to revisit what the “scene” meant to its patrons, as well as what disco might mean commercially to new generations. But rarely do the songs in this type of film serve as anything but collective backdrop or the means by which a filmmaker might establish setting, particularly in terms of a decade. They merely reconfigure radio programming, reorder Top 40 hits for a theatrical space. © 2001 Taylor & Francis Group, LLC.
3 citations (Crossref) [2023-10-31]
Keywords: dept.eng

Charles Brockden Brown's Ormond, property exchange, and the literary marketplace in the early American republic - Ellis, S. (Studies in the Novel, 2005)
Keywords: dept.eng; ⛔ No DOI found

The paper bag principle: Of the myth and the motion of colorism - Kerr, A.E. (Journal of American Folklore, 2005)
This article, extracted from a larger study, is attentive to the national folk culture of African-American communities - especially rumor and legend - in a number of city centers. The study begins with Washington, D.C., as a representative model to examine the role of complexion-related lore in black neighborhoods, organizations, and institutions, and then extends outward to other urban areas. Complexion lore, the article argues, functioned as a sophisticated negotiation of racism, wherein black residents complicated American urban principles of inclusion and exclusion by integrating color notions into institutional oral history. Copyright © 2005 by the Board of Trustees of the University of Illinois.
25 citations (Crossref) [2023-10-31]
Keywords: dept.eng; dept.wgs

The economics of authorship: Online paper mills, student writers, and first-year composition - Ritter, K. (College Composition and Communication, 2005)
Using sample student analyses of online paper mill Web sites, student survey responses, and existing scholarship on plagiarism, authorship, and intellectual property, this article examines how the consumerist rhetoric of the online paper mills construes academic writing as a commodity for sale, and why such rhetoric appeals to students in first-year composition, whose cultural disconnect from the academic system of authorship increasingly leads them to patronize these sites.
Keywords: dept.eng; ⛔ No DOI found

Reviewers reviewed: John Davis and the early American leterary field - Ellis, S. (Early American Literature, 2007)
1 citations (Crossref) [2023-10-31]
Keywords: dept.eng

Opinion: Ethos interrupted: Diffusing "star" pedagogy in creative writing programs - Ritter, K. (College English, 2007)
Keywords: dept.eng; ⛔ No DOI found

Popular millenarianism and empire in Blake's night thoughts - Rosso, G.A. (Blake, Modernity and Popular Culture, 2007)
Journal Abbreviation: Blake, Mod. and Popul. Cult.
Keywords: dept.eng

Empathy and identity in Vernon Lee's Hauntings - Fluhr, N. (Victorian Studies, 2006)
0 citations (Crossref) [2023-10-31]
Keywords: dept.eng

Freud as new woman writer: Maternal ambivalence in Studies on Hysteria - Fluhr, N. (English Literature in Transition, 1880-1920, 2010)
Keywords: dept.eng; ⛔ No DOI found

Woolf’s editorial self-censorship and risk-taking in Jacob’s room - Neverow, V. (Virginia Woolf and the Literary Marketplace, 2010)
Journal Abbreviation: Va. Woolf and the Literary Marketpl.
Keywords: dept.eng

Virginia Woolf and city Aesthetics - Neverow, V.S. (The Edinburgh Companion to Virginia Woolf and the Arts, 2010)
Journal Abbreviation: The Edinburgh Companion to Virginia Woolf and the Arts
Keywords: dept.eng

Latin Alive: The survival of Latin in English and the Romance languages - Solodow, J.B. (Cambridge University Press, 2010)
In Latin Alive, Joseph Solodow tells the story of how Latin developed into modern French, Spanish, and Italian, and deeply affected English as well. Offering a gripping narrative of language change, Solodow charts Latin's course from classical times to the modern era, with focus on the first millennium of the Common Era. Though the Romance languages evolved directly from Latin, Solodow shows how every important feature of Latin's evolution is also reflected in English. His story includes scores of intriguing etymologies, along with many concrete examples of texts, studies, scholars, anecdotes, and historical events; observations on language; and more. Written with crystalline clarity, this is the first book to tell the story of the Romance languages for the general reader and to illustrate so amply Latin's many-sided survival in English as well. © Joseph B. Solodow 2010.
Journal Abbreviation: Latin Alive: The Survival of Latin in Engl. and the Roman. Languages Pages: 356 Publication Title: Latin Alive: The Survival of Latin in Engl. and the Roman. Languages
Keywords: History; History; Latin language; Influence on English; Romance languages; Influence on Romance; Latin language; Latin language; dept.eng; faculty_collection

"Telling what's o'er": Remaking the sonnet cycle in Augusta Webster's Mother and Daughter - Fluhr, N. (Victorian Poetry, 2011)
0 citations (Crossref) [2023-10-31]
Keywords: dept.eng

Endless virtue and trinitarian prayer in lancelot’s healing of urry - Holbrook, S.E. (Malory and Christianity: Essays on Sir Thomas Malory's Morte Darthur, 2013)
Journal Abbreviation: Malory and Christianity: Essays on Sir Thomas Malory's Morte Darthur
Keywords: dept.eng

To the well: Malory's Sir Palomides on ideals of chivalric reputation, male friendship, romantic love, religious conversion-and loyalty - Holbrook, S.E. (Arthuriana, 2013)
Although Palomides in Malory's Morte Darthur and his counterpart in the French Tristan en Prose are usually discussed by their roles, my study selects five scenes linked by woodland settings, wells, and complaints. Accordingly, it demonstrates what each scene shows about the values of reputation, friendship, love, religious conviction, and-in the aftermath of the rupture between Lancelot and Arthur-the capacity for loyalty to Lancelot shown by Palomides and his brother Saphir. © 2013 Project MUSE.
0 citations (Crossref) [2023-10-31]
Keywords: dept.eng

Representing the modern animal in culture - Dubino, J.; Rashidian, Z.; Smyth, A. (Palgrave Macmillan, 2014)
Examining a wide range of works, from Gulliver's Travels to The Hunger Games, Representing the Modern Animal in Culture employs key theoretical apparatuses of Animal Studies to literary texts. Contributors address the multifarious modes of animal representation and the range of human-animal interactions that have emerged in the past 300 years. © Jeanne Dubino, Ziba Rashidian, and Andrew Smyth 2014. All rights reserved.
Keywords: Animals in literature; Human-animal relationships in literature; Animals and civilization; dept.eng; faculty_collection

Splicing genes with postmodern teens: The hunger games and the hybrid imagination - Smyth, A. (Representing the Modern Animal, 2014)
Journal Abbreviation: Represent. the Mod. Anim. in Cult.
Keywords: dept.eng

Hawthorne's Two Bodies: Politics and Aesthetics in Our Old Home - Baraw, C. (Literary Imagination, 2016)
0 citations (Crossref) [2023-10-31]
Keywords: dept.eng

Challenging evaluation: The complexity of grading writing in hybrid MOOCs - McEachern, R.W. (Handb. of Res. on Writ. and Compos. in the Age of MOOCs, 2017)
When MOOCs exploded into the public consciousness in 2012, many supporters touted their potential to disrupt higher education. In a short time, MOOCs have evolved, and that role as radical change agents seems to have faded. However, the use of Hybrid MOOCs, in which onground courses use MOOCs for some or all of their content, does have the potential to be disruptive, albeit on a smaller scale. This article will describe one Hybrid MOOC and the ways it could be used to disrupt individual pedagogy, and perhaps affect larger change as a result. © 2017 by IGI Global. All rights reserved.
Journal Abbreviation: Handb. of Res. on Writ. and Compos. in the Age of MOOCs
Keywords: dept.eng

Swinburne: Criticism as perversion - Fluhr, N. (Nineteenth Century Prose, 2016)
Keywords: dept.eng; ⛔ No DOI found

Postmodernism and the politics of “culture” - Katz, A. (Taylor and Francis, 2000)
Postmodernism and the Politics of ‘Culture’ is a comparative critical analysis of the political and intellectual ambitions of postmodernist critical theory and the academic discipline of cultural studies. Katz’s polemical aim is to show that cultural studies comes up short in both areas, because its practitioners focus on too-narrow issues-primarily, celebrating the folkways of micro-communities-while denying the very possibility of studying, understanding, and changing society in any comprehensive way and to any universally beneficial purpose. He argues that scholars and activists alike would do well to make use of the analytical tools of postmodernist critical theory, whose practitioners acknowledge the political significance of the differences between social groups, but do not consider them to be unbridgeable, and so seek to develop a set of practices for creating a truly inclusive, truly democratic public sphere. © 2000 Taylor & Francis. All rights reserved.
Journal Abbreviation: Postmodernism and the Politics of "Culture" Pages: 237 Publication Title: Postmodernism and the Politics of "Culture"
Keywords: dept.eng

The life and times of chinua achebe - Ogbaa, K. (2021)
The Life and Times of Chinua Achebe introduces readers to the life, literary works, and times of arguably the most widely-read African novelist of recent times, an icon, both in continental Africa and abroad. The book weaves together the story of Chinua Achebe, a young Igboman whose novel Things Fall Apart opened the eyes of the world to a more realistic image of Africa that was warped by generations of European travelers, colonists, and writers. Whilst continuing to write further influential novels and essays, Achebe also taught other African writers to use their skills to help their national leaders to fight for their freedoms in the post-colonial era, as internal warfare compounded the damage caused by European powers during the colonial era. In this book Kalu Ogbaa, an esteemed expert on Achebe and his works, draws on extensive research and personal interviews with the great man and his colleagues and friends, to tell the story of Achebe and his work. This intimate and powerful new biography will be essential reading for students and scholars of Chinua Achebe, and to anyone with an interest in the literature and post-colonial politics of Africa. © 2022 Kalu Ogbaa.
Pages: 1-228 tex.document_type: Book tex.source: Scopus
Keywords: dept.eng

Landscape in Middle English Romance: The Medieval Imagination and the Natural World - Richmond, Andrew M. (Cambridge University Press, 2021)
"In Sir Isumbras, one of the most enduringly popular late medieval romances, the penitential experience of its eponymous hero (modeled off of the evergreen St. Eustace tales) is grounded in a careful exploration of hillside ironmines and the communities of smiths that rely upon them. Such an interest in natural resource management and industrial development derives from the notable focus on charting topography that distinguishes the central third of the romance - marking Isumbras's transition from secular to divine systems of values, and his geographical movement from Christian to Saracen lands. Similarly, in the fourteenth-century Middle English version of William of Palerne (hereafter William), the eponymous protagonist flees with his lover, Melior, through a world of forests and bays that overflows with topographical details. These intricate explanations of quarry pits, hollow oaks, roadside groves, seaside caves, and war-torn estates together compose a perspective on landscape defined by networks of economic exchange. In this regard, the predominant view of the natural world presented in William ties it to earlier romances such as Havelok the Dane, a text interested in the systems of exchange that knit seaside fishermen to urban markets; and to later texts such as the Middle English versions of Partonope of Blois, which demonstrates in its depictions of estates the mercantile and agricultural uses of natural spaces that underlie the successful maintenance of a noble identity. This chapter, then, will discuss how Middle English romances' attention to the management and harvest of natural resources often reveals the link between country and urban spaces created by the exchange of such goods. I will also consider how sympathetic portrayals of laborers and other low-class harvesters of natural resources suggest that romances, particularly around the turn of the fifteenth century, reflect the shifting nature of their bourgeois-gentry audience by engaging with the environmental experiences of merchants, household clerks, reeves, franklins, and gentry farmers in addition to those of the higher aristocracy"–
SCSU Faculty Scholar Award
Keywords: History and criticism; English literature; History and criticism; Landscapes in literature; Seashore in literature; Middle English; 1100-1500; Romances; English; SCSU Faculty Scholar Award; award_winner; dept.eng

Lord of the Forest | Good Fences - Sonnenschein, Dana (Kosmos Journal, 2021)
Keywords: dept.eng; peer-reviewed; ⛔ No DOI found

Reflections: neurology and the humanities. You had the choice, Martha. - Shipley, Vivian (Neurology, 2009)
0 citations (Crossref) [2023-10-31] Place: United States Shipley, Vivian. Southern Connecticut State University, 501 Crescent Street, New Haven, CT 06515, USA. shipleyv1@southernct.edu
Keywords: *Abortion; Induced/es [Ethics]; *Abortion; Induced/px [Psychology]; *Caregivers/px [Psychology]; *Lesch-Nyhan Syndrome/ge [Genetics]; *Maternal Behavior/px [Psychology]; *Neurology/es [Ethics]; Abortion; Induced; Adult; Caregivers; Choice Behavior; Choice Behavior/es [Ethics]; Female; Humans; Infant; Lesch Nyhan syndrome; Lesch-Nyhan Syndrome; Lesch-Nyhan Syndrome/pp [Physiopathology]; Male; Maternal Behavior; Muscle Weakness; Muscle Weakness/ge [Genetics]; Neurology; Poetry as Topic; Self-Injurious Behavior; Self-Injurious Behavior/ge [Genetics]; Self-Injurious Behavior/pc [Prevention & Control]; adult; article; automutilation; caregiver; decision making; dept.eng; ethics; female; genetics; human; induced abortion; infant; literature; male; maternal behavior; muscle weakness; neurology; pathophysiology; psychological aspect

Meeting the Dire Wolf – Dana Sonnenschein - Sonnenschein, Dana (panoply, a literary zine, 2021)
Not just heavy bones. The huge skull fleshed, broad across the brow and muzzle, 3” canines, thick neck and body — the wolf of your nightmares and not just one. Thirty. A pack drawn to the sce…
Keywords: dept.eng

Winter's Orphan - Sonnenschein, Dana (O:JA&L (Open: Journal of Arts & Letters), 2021)
Keywords: dept.eng; ⛔ No DOI found

Empirical insights into college students’ academic reading comprehension in the united states - Kalbfleisch, Elizabeth; Schmitt, Elena; Zipoli, Richard P. (Journal of College Reading and Learning, 2021)
This article reports on a collaborative research project involving faculty in writing studies, communication disorders, and applied linguistics that sought to empirically describe the reading skills of students (N = 910) in freshman composition classes at one college and two universities in the northeast United States. The research team developed and administered a questionnaire that evaluated students’ reading abilities according to six categories: inferential ability, background knowledge, general comprehension, vocabulary, figurative language/jargon, and morphosyntactic structures (grammar/syntax). Our statistically significant results showed that students scored best in the categories of background knowledge and general comprehension, which are well researched in a college population. However, students struggled in categories such as figurative language/jargon and morpho-syntactic structures, which are not well researched in a college population. Further, comprehension seemed generally discrete (understanding specific points of an essay) rather than holistic (indicated by an ability synthesize those points into a general statement about the author’s thesis). These findings suggest that further empirical research in this area will help describe the reading skills of college students and consequently will inform the development of pedagogical approaches that more effectively address students’ current needs. © 2021 College Reading and Learning Association.
2 citations (Crossref) [2023-10-31] Type: Article tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85101017685
Keywords: dept.cmd; dept.eng; dept.wll; peer-reviewed

Mistress of Snow - Sonnenschein, Dana (Gingerbread House Literary Magazine, 2021)
Hinges creak, and she swirls in the door, puts her finger to blue lips. Cold takes the old woodcutter, eyes open, breath frozen in his beard. But crystals melt in your lashes as you gaze on her gl…
Keywords: dept.eng

The Emotional Effects of Literacy: Vietnamese Women Negotiating the Shift to a Market Economy - Crawford, I.W. (WOMEN and LITERACY, 2007)
Vietnam's 1986 doi moi reforms are transforming Vietnam from a socialist economy to a socialist market economy. In addition to liberalized laws allowing
Keywords: dept.eng

Becoming allies accomplices: Problematizing the intersection of reflection and action through pre-service teachers’ autoethnographies as praxis - Sinclair, Meredith N; Powell, Jessica S (International Journal of Critical Pedagogy, 2020)
This paper explores the phenomenon of pre-service teachers becoming accomplices for racial justice. Using hermeneutic phenomenology, we examine the experiences of three white, female pre-service teachers navigating this terrain. A framework we are naming autoethnography as praxis emerged from this inquiry. Our research interrogates the notion of white allies and the intersection of critical dialogue and action in pre-service teacher education. Building off of perspectives in critical race and critical whiteness studies, this work is grounded in the reality of the material permanence of white supremacy that white teachers must acknowledge and develop tools to dismantle. Autoethnography as praxis moves students from simply analyzing and reporting their experiences (including their emerging understanding of white privilege) through autoethnography to examining how their experiences have shaped and will continue to shape their identities and practices as teachers. By reframing autoethnography as a dialogue between researcher and her texts, we hope to push beyond reflection to action. By engaging participants in reflection on their actions, autoethnography as praxis also addresses the flaw of white teachers acting as benevolent allies who set their own agenda and position people of color as “needing their assistance.” © 2020, University of North Carolina at Greensboro. All rights reserved.
tex.ids: sinclairBecomingAlliesAccomplices2020a tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85084794698 type: Article
Keywords: Anti-racist pedagogy; Praxis; Social justice; Teacher education; Whiteness; dept.cur; dept.eng; peer-reviewed; ⛔ No DOI found

Mary Johnson of Wethersfield, Connecticut, hanged for witchcraft, 1648 (poem) - Shipley, Vivian (Connecticut Literary Anthology: Celebrating Nutmeg Authors, 2020, 2020)
Connecticut Literary Anthology features thirty-six Connecticut poets and prose writers from across the Nutmeg State. The 2020 Anthology is published by the Central Connecticut State University English Department. The writers in the inaugural anthology share themes amplified by current events, but not the context. Stories of family, economic in- equality, sexual violence, social justice, culture wars, lost love, aging, and gender—they’re all in here. And mangoes. Everyone loves mangoes. Featured writers: Janet L. Bannister, Charles V. Belson, Susan Cinoman, Ginny Lowe Connors, Jason Courtmanche, Catherine DeNunzio, Joanie DiMartino, Catherine DeNunzio, Meghan Evans, Maura Faulise, Kathryn Fitzpatrick, Beth Gibbs, Cecilia Gigliotti, Nichole Gleisner, Sitara Gnanaguru, Emi Gonzalez, José B. González, Benjamin S. Grossberg, Avery Jenkins, B. Fulton Jennes, Sarah Darer Littman, Kiran Masroor, Melissa McEwen, Claudia McGhee, Nancy McMillan, Jean P. Moore, Steven Ostrowski, Makenzie Ozycz, Aimee Pozorski, Kara Molway Russell, Vivian Shipley, Amy Sisson, Katherine A. Szpekman, Wendy Terry, Mika Taylor, Marina Tinone, Jason Wilkins. Praise for Anthology: "It feels like we have become unglued from one another since March of 2020; masked strangers passing each other in anonymity. But this anthology glues us back together and helps us find ways to heal and talk with one another. Important stories are told, and we should heed them." —Lisa Comstock, Director for Connecticut Center for the Book
Keywords: dept.eng

Maps for Jackie - Labbe, Jason (BlazeVOX Books, 2020)
"Poetry's natural habitat is one of detail, radiant or tarnished, an intimate geography that draws us close to where presence is an act of perception: world into word. In Maps for Jackie, Jason Labbe navigates a terrain of singular encounters and incidents, tactile, luminous and animated by the sensuous abrasions and comforts of the heartmind as they touch down on his, and our, present: white leaf is like a moth / wing I'd fix to her shoulder.–Ann Lauterbach"–The back cover
Keywords: 21st century; American poetry; dept.eng; faculty_collection

An American perspective on equal educational opportunities - Russo, C; Perkins, B (Perspectives in Education, 2004)
The United States Supreme Court ushered in a new era in American history on May 17, 1954 in its monumental ruling in Brown v Board of Education, Topeka, Kansas. Brown is not only the Court's most significant decision on race and equal educational opportunities, but also ranks among the most important cases it has ever decided. In Brown a unanimous Court struck down the pernicious doctrine of “separate but equal” in holding that the de jure segregation of students in public schools on the basis of race deprived minority children of equal educational opportunities in violation of the Equal Protection Clause of the Fourteenth Amendment. In addition to its impact on school desegregation, Brown has been the catalyst for revolutionary change influencing just about every facet of American society. Given the breadth of changes that it spawned, this article briefly reviews the Supreme Court's ruling in Brown before turning to the two most important educational areas where it has been the key, namely special education and sexual harassment.
tex.unique-id: ISI:000223927200004
Keywords: dept.eng; ⛔ No DOI found

Michelangelo's Captive - Sonnenschein, Dana (The Ekphrastic Review, 2020)
Michangelo’s Captive ​ I wished to photograph a beautiful man sculpted by Michelangelo, afraid I would forget him if I did not, for he had no story, no name. But I turned away. I had the...
Keywords: dept.eng; ⛔ No DOI found

The letter and the law, or how caroline norton (Re)Wrote female subjectivity - Fluhr, Nicole (Tulsa studies in women's literature, 2009)
Citation Key Alias: lens.org/189-883-465-763-54X tex.type: [object Object]
Keywords: dept.eng; ⛔ No DOI found

Emotional Expression in Malory's Elaine of Ascolat - Holbrook, Sue Ellen (Parergon, 2007)
Shrieks and complaints, accompanied by body language, contribute markedly to Malory's representation of Elaine of Ascolat's emotionality. Elaine's two shrieks echo Lancelot's and indicate change from sorrow for a wounded beloved to heartbreak when he rejects her. When Elaine is compared with speakers in love lyrics, allegories, and romances, the thoughts in her unarticulated complaints after the pained second shriek may be understood and related to her defence of complaint and perseverance in love despite rejection. Similarly, Elaine's complaint letter, including its overlooked moan to ladies, reflects a state of tranquility and brings about a just resolution.
0 citations (Crossref) [2023-10-31]
Keywords: dept.eng

Incorporating reflection into business communication service-learning courses: - Mceachern, Robert W (Business Communication Quarterly, 2006)
2 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/035-763-141-032-563 tex.type: [object Object]
Keywords: dept.eng

Utility, artistry, and narrative control in Herman Melville's "The Bell-Tower" - Ellis, Scott (College Literature, 2020)
0 citations (Crossref) [2023-10-31]
Keywords: dept.eng; peer-reviewed

"Train & Pool," “The Colonel Takes a Position," "Summer Almanac," "Cloud Study," "Light, A Reagent," Author's Statement: "Writing, For and To" - Johnson, Brian (Parhelion, 2020)
Keywords: dept.eng; ⛔ No DOI found

"Asides" and "Household" - Johnson, Brian (Court Green, 2020)
Keywords: dept.eng; ⛔ No DOI found

Maple Street, London (1915) - Johnson, Brian (The Ekphrastic Review, 2020)
Keywords: dept.eng; ⛔ No DOI found

Rhubarb Leaf - Johnson, Brian (great weather for MEDIA, 2020)
Keywords: dept.eng; peer-reviewed; ⛔ No DOI found

Tour - Johnson, Brian (The Main Street Rag, 2020)
Keywords: dept.eng; ⛔ No DOI found

W. D. Howells, William James, and the pragmatist pluralism of “The Angel of the Lord” - Petrie, Paul (American Literary Realism, 2020)
0 citations (Crossref) [2023-10-31] tex.ids: petrieHowellsWilliamJames2020a tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85091388735 type: Review
Keywords: dept.eng

Negotiating pedagogical authority: the rhetoric of writing center tutoring styles and methods - Corbett, Steven J (Rhetoric Review, 2013)
Writing centers have long been rich sites of critical inquiry into individualized instructional styles and methods. One of the great writing center debates involves directive versus nondirective tutoring styles and methods. While many writing center scholars have discussed the intricacies of directive or interventionist versus nondirective or minimalist pedagogical methods, few have examined the rhetorical implications of this important debate in relation to more classroom-based peer collaborations. This article rhetorically analyzes the literature on directive/nondirective methods and various approaches to tutoring writing, drawing pedagogical and rhetorical connections and implications useful for all teachers of writing and rhetoric. © 2013 Copyright Taylor & Francis Group, LLC.
4 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/159-402-799-690-469 tex.type: [object Object]
Keywords: dept.eng

‘The Author Makes the Reader Acquainted with His Abode’: Hawthorne as Transatlantic Tour Guide in The Marble Faun and ‘The Old Manse’ - Baraw, Charles (Transatlantic Literature and Author Love in the Nineteenth Century, 2016)
Here the volume continues its reflections on Hawthorne’s career but turns to his place in the literature of ‘homes and haunts’, taking up the question of how literary geography and its localization of authors helped construct an authorial presence for Americans and a tangible transatlantic literary canon. (It turns out that having a home on the literary itinerary was crucial to nineteenth-century reception.) Baraw demonstrates that the poetics of literary tourism provided Hawthorne with both a means of self-canonization as a tourist attraction and a tool for cultivating the ideal ‘English’ reader for his books. This essay begins a strand of chapters related to literary tourism and the construction of international heritage landscapes.
Citation Key Alias: lens.org/027-169-429-746-184
Keywords: American Author; Authorial Persona; Direct Address; Tour Guide; Tourist Attraction; dept.eng

Pain as semiosomatic force: The disarticulation and rearticulation of subjectivity - Larocco, Steve (Subjectivity, 2016)
Scarry's (The Body in Pain: The Making and Unmaking of the World, Oxford, New York, 1985) broke crucial ground in examining the antagonisms between pain, embodiment and language, and the isolating effects of pain as experience. This paper submits Scarry's claim that extreme pain destroys language, evades mediation, and isolates the subject to critical scrutiny, arguing instead that pain is a semiosomatic force, a form of feeling generated by imperative information about embodiment (real or imaginary) that works to disarticulate and move the subject and the social environment. Pain is not predominantly antagonistic to language; rather, pain insists on signifying, with language being only one of its performative media. What pain resists is representation, not the informational force exerted through language and other semiotic forms. Rather than unmaking language, pain disarticulates and rearticulates subjectivity, refashioning interrelations between the body, subjectivity, others, and culture in ongoing processes of largely aversive impingement, embroiling subjectivity with the imperative directives of embodied vulnerability. © 2016 Macmillan Publishers Ltd.
3 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/031-246-870-419-636 tex.type: [object Object]
Keywords: dept.eng; embodiment; pain; performativity; semiotics; subjectivity

Invisible debility: attitudes toward the underrepresented in library workplaces - Brown, Mary E (Public Library Quarterly, 2015)
The American Library Association is committed to recruiting persons of color and those with disabilities to the profession, yet these groups are underrepresented among librarians. While intentional discrimination was the impetus for the Civil Rights Act of 1964, empirical studies in the workplace have exposed continued discrimination through unconscious bias. Extending such research to the library profession raises the question: How do librarians perceive the underrepresented as potential fellow library staff? In my recently conducted study of public library staff and future librarians, participants agreed that library staff should represent the diversity of the communities served; there was little support, however, for actively attempting to advance proportional representation through education or hiring. © , Published with license by Taylor & Francis.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/040-376-541-767-199 tex.type: [object Object]
Keywords: dept.eng; employment discrimination; hiring bias; peer-reviewed; underrepresentation of minorities in library employment

Is Personality a System? Stability, Process and Plasticity. - Larocco, Steven (Integrative psychological & behavioral science, 2015)
The nomothetic thrust of personality research has been the subject of some significant recent criticism. One major problem is the failure in much personality research to sufficiently scrutinize its methods and its background beliefs. This produces conceptual schematizations of personality that do not sufficiently take into account the disunity and plasticity that affects what is construed as personality; it also underplays the necessity of more fully theorizing the network of infrapsychic and transpersonal systems, processes, structures, templates, interfaces, flows of stimuli, qualities of embodiment and contingencies that dynamically manifest as personality. It is through unfolding the complexity inherent in this network that personality theorization can move forward in new ways. This paper provides a provisional, beginning taxonomy of this network in order to start a research dialogue about personality that doesn't begin with the operative background beliefs of nomothetic methodology, that doesn't tacitly or overtly construe the individual to be a self-regulating, homeostatic system, and that resists presupposing personality as a cohesive, stable quality of personhood.
1 citations (Crossref) [2023-10-31] Place: United States Larocco, Steven. Southern Connecticut State University, New Haven, CT, USA. laroccos1@southernct.edu.
Keywords: *Personality; *Psychological Theory; Contingency; Embodiment; Five-factor model; Humans; Personality; Personality/cl [Classification]; Plasticity; Plasticizer; Psychological Theory; Stabilizer; classification; dept.eng; human; personality; psychological theory

Ideology, affect, semiotics: towards a non-personal theory of personality. - Larocco, Steve (Integrative psychological & behavioral science, 2014)
Personality theories, as Giordano (2014) argues, often treat Western versions of the self as having universal import. Eastern notions of self, however, offer a dramatically different basis for thinking about what personality might be. This paper, nonetheless, seeks to offer a general framework for theorizing about the epiphenomenon of personality in any culture, asserting that it is an effect of specific histories of ideological practices, semiotic networks and systems, and affect, which engage each other in dialogic and dialectical ways. The interactions of these factors, guided by ideology, regularize behavior and affective dynamics, largely in non-personal ways. Subjects are produced and reproduced from these complex interactions, which are situationally specific and simultaneously transpersonal. The subjects formed through these interactions are the basis for the folk psychology of personality, which treats the transient, varying effects of these interactions as more or less reified qualities that form a basis for the construction of selfhood, however conceived.
3 citations (Crossref) [2023-10-31] Place: United States Larocco, Steve. Southern Connecticut State University, New Haven, CT, USA, laroccos1@southernct.edu.
Keywords: *Affect; *Culture; *Personality; *Psychological Theory; Affect; Culture; Five-Factor Model; Humans; Ideology; Personality; Psychological Theory; Semiotics; affect; cultural anthropology; dept.eng; human; personality; psychological theory

Experiencing a social network in an organizational context the facebook internship - Mceachern, Robert W (Business Communication Quarterly, 2011)
As Facebook becomes increasingly more popular as a communication tool for businesses and organizations, it is important that our students learn to transfer personal Facebook skills to professional settings. This article focuses on the lessons learned by two students who used Facebook as part of a social media internship, as well as what the author learned about its use through research and teaching a course on social media and professional writing. © 2011 Association for Business Communication.
12 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/101-977-826-729-780 tex.type: [object Object]
Keywords: Facebook; dept.eng; internships; social media

Guenevere: the abbess of amesbury and the mark of reparation - Holbrook, Sue Ellen (Arthuriana, 2010)
Malory elevates Guenevere to abbess ofAmesbury where she heals her soul through a penitential process clarified by Cassian's teachings on attitude and supplication and by the cloister context and devotional formulas of her speech on salvation. (SEH).
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/102-712-156-403-804 tex.type: [object Object]
Keywords: dept.eng

Milton - Rosso, G. A. (William Blake in Context, 2019)
Keywords: dept.eng; faculty_collection

Brown and the Yellow Fever - Ellis, Scott (The Oxford Handbook of Charles Brockden Brown, 2019)
The Oxford Handbook of Charles Brockden Brown provides an up-to-date survey of the life of and full range of writings by Charles Brockden Brown (1771–1810), a key writer of the Atlantic revolutionary age and U.S. Early Republic. Through the late twentieth century, Brockden Brown was best known as an important author of political romances in the gothic mode that were widely influential in romantic era, and has generated large amounts of scholarship as a crucial figure in the history of the American novel. More recent work recognizes him likewise an influential editor, historian, and writer in other genres such as poetry, short fiction, and essays, and as a figure whose work resonated throughout the Atlantic world of the revolutionary age. The Oxford Handbook’s thirty-five chapters build on the research of the most recently scholarly generation to introduce readers to and explore Brown’s wide-ranging work. Its chapters focus on the author’s biography, romances, writings in a range of genres, his key concept of the romance as a form of engaged conjectural history, his engagements in the cultural-ideological struggles of the revolutionary and Napoleonic eras, as well as the aesthetic, political, scientific, and other key dimensions of his corpus. The volume concludes with a survey of Brown’s complex reception history and the state of Brown studies at present.
Citation Key Alias: ellisBrownYellowFever2019a, lens.org/084-330-565-542-747
Keywords: dept.eng; faculty_collection

An Archaeology of Days - Shipley, Vivian (Negative Capability Press, 2019)
An Archaelogy of Days contains new poetry from Vivian Shipley. Connecticut State University Distinguished Professor, Vivian Shipley teachesat Southern Connecticut State University where she was named FacultyScholar in 2000, 2005 and 2008. Her eleventh book, Perennial, was publishedin 2015 by Negative Capability Press and was nominated for the PulitzerPrize and named the Paterson Poetry Prize Finalist. The Poet, her tenth book,was published in 2015 by Louisiana Literature Press, Southeastern LouisianaUniversity. All of Your Messages Have Been Erased (Louisiana Literature Press,SLU, 2010) was nominated for the Pulitzer Prize, won the Sheila MottonBook Prize from the New England Poetry Club, the Paterson Award forSustained Literary Achievement and the CT Press Club Award for BestCreative Writing. Her sixth chapbook is Greatest Hits: 1974-2010 (PuddingHouse Press, Youngstown, Ohio, 2010). She has received the Library ofCongress’s Connecticut Lifetime Achievement Award for Service to theLiterary Community and a Connecticut Book Award for Poetry two times.Most recently, she won the 2017-18 Steve Kowit Prize for Poetry for “Cargo”from San Diego Arts & Entertainment Guild. In 2015, she won the HackneyLiterary Award for Poetry for “Foxfire.”
Keywords: 21st century; American poetry; dept.eng; faculty_collection

Unsettling transcription through “event memory”: problem and possibility in exploring the phenomenological question - Sinclair, Meredith N. (Qualitative Inquiry, 2020)
This article works to unsettle the use of transcription in qualitative inquiry by troubling the truth claims of transcribed text. Building on the hermeneutic phenomenology of Van Manen, it explores the way the researcher might “write through” transcribed text to return to the two-dimensional text space a more honest reading of lived experience. It also draws on Deleuze and Guattari’s rhizomatic thinking to explore the “gruesome multiplicities” present in reality—and the ways we might honor that multiplicity in research texts. Excerpts from an inquiry into the phenomenon of “reading as not a reader” are used to illustrate.
1 citations (Crossref) [2023-10-31] tex.ids: lens.org/070-679-779-525-700, pop00318, sinclairUnsettlingTranscriptionEvent2018, sinclairUnsettlingTranscriptionEvent2018a, sinclairUnsettlingTranscriptionEvent2020a tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85059284090 tex.type: [object Object] type: Article
Keywords: dept.eng; hermeneutic phenomenology; methodologies; methods of inquiry; peer-reviewed; qualitative research; qualitative research and education; transcription; writing as method of inquiry

Pinkwashing - Blackmer, Corinne E. (Israel Studies, 2019)
5 citations (Crossref) [2023-10-31]
Keywords: dept.eng; peer-reviewed

Louise Rosenblatt: The reader, democracy, and the ethics of reading - Sinclair, Meredith N. (Reading as Democracy in Crisis: Interpretation, Theory, History, 2019)
Reading as Democracy in Crisis: Interpretation, Theory, History explores the dialectic between historical conditions and the reading strategies that arise from them. It explores the relationship...
Keywords: dept.eng

The Other, Shame, and Politics: Levinas, Justice, and Feeling Responsible - Larocco, Steve (Religions, 2018)
Adi Ophir has suggested that the political realm is an order of evils, producing and managing regular forms of suffering and violence rather than eliminating them. Thus, the political is always to some extent a corrupted order of justice. Emmanuel Levinas’ work presents in its focus on the face-to-face relationship a means of rethinking how to make the political more open to compassionate justice. Though Levinas himself doesn’t sufficiently take on this question, I argue that his work facilitates a way of thinking about commiserative shame that provides a means to connect the face-to-face to its potential effects in the political sphere. If such shame isn’t ignored or bypassed, it produces an unsettling relation to the other that in its adversity motivates a kind of responsibility and care for the other that can alter the public sphere.
2 citations (Crossref) [2023-10-31]
Keywords: Commiseration; Evil; Guilt; Law; Levinas; Other; Politics; Responsibility; Shame; Sympathy; commiseration; dept.eng; evil; guilt; law; other; peer-reviewed; politics; responsibility; shame; sympathy

Teaching race, gender, and narrative form in Gertrude Stein’s “Melanctha.’ - Blackmer, Corinne E. (Approaches to Teaching the Works of Gertrude Stein, 2018)
A trailblazing modernist, Gertrude Stein studied psychology at Radcliffe with William James and went on to train as a medical doctor before coming out as a lesbian and moving to Paris, where she collected contemporary art and wrote poetry, novels, and libretti. Known as a writers writer, she has influenced every generation of American writers since her death in 1946 and remains avant-garde.Part 1 of this volume, Materials, provides information and resources that will help teachers and students begin and pursue their study of Stein. The essays of part 2, Approaches, introduce major topics to be covered in the classroomrace, gender, feminism, sexuality, narrative form, identity, and Steins experimentation with genrein a wide range of contexts, including literary analysis, art history, first-year composition, and cultural studies.
Keywords: dept.eng

The divine sublime: Educating spiritual teachers in Emerson’s divinity school address - Blackmer, Corinne E. (Approaches to Teaching the Works of Ralph Waldo Emerson, 2018)
A leader of the transcendentalist movement and one of the country's first public intellectuals, Ralph Waldo Emerson has been a long-standing presence in American literature courses. Today he is remembered for his essays, but in the nineteenth century he was also known as a poet and orator who engaged with issues such as religion, nature, education, and abolition.This volume presents strategies for placing Emerson in the context of his time, for illuminating his rhetorical techniques, and for tracing his influence into the present day and around the world. Part 1, "Materials," offers guidance for selecting classroom editions and information on Emerson's life, contexts, and reception. Part 2, "Approaches," provides suggestions for teaching Emerson's works in a variety of courses, not only literature but also creative writing, religion, digital humanities, media studies, and environmental studies. The essays in this section address Emerson's most frequently anthologized works, such as Nature and "Self-Reliance," along with other texts including sermons, lectures, journals, and poems.
Google-Books-ID: qseCDwAAQBAJ
Keywords: Language Arts & Disciplines / Study & Teaching; Literary Criticism / American / General; Literary Criticism / Modern / 19th Century; dept.eng

Reading curriculum in the age of spectacle: Reclaiming experience and dialogue in reading - Sinclair, Meredith N. (Journal of Curriculum Theorizing, 2018)
Using Fahrenheit 451 as a model for reading in the age of spectacle, this paper offers a critique of reading curriculum driven by Common Core State Standards for English Language Arts and Literacy in History/Social Studies, Science, and Technical Subjects (CCSS-ELA), which divorces reading from dialogue and lived experience. Drawing on Debord’s (1967/1983) notion of spectacle, the author considers how our current cultural moment may be shaping and shaped by an alienated and alienating curriculum of reading. By embracing the political implications of reading curriculum, we can reclaim reading as a dialogic activity grounded in the world.
Citation Key Alias: lens.org/181-243-807-539-577, pop00288 tex.type: [object Object]
Keywords: dept.eng; literacy; peer-reviewed; reading; ⛔ No DOI found

Fluid boundaries in 'The Awntyrs off Arthure' and 'Sir Isumbras' - Richmond, Andrew (Open Library of Humanities, 2018)
Encounters with water shape the Middle English romances of The Awntyrs off Arthure and Sir Isumbras. In the latter, rivers and the 'Greek Sea' serve to distinguish separate sections of the narrative: the river marks the point at which the titular hero's family unit begins to break down, while the beach of the sea marks the lowest point of his social power. Yet his later traversal of the Greek Sea itself allows him to reassemble his family and reclaim his aristocratic power. In Awntyrs, the Tarn Wathelene (or Wadling) ties the actions of the romance's first episode onto a specific spot in the real-world English landscape, while connecting the text to a number of other Arthurian romances that also mention or take place near the tarn. This article, then, argues that the waterscapes in these two texts illustrate a late-medieval understanding of tarns, rivers, and seas as explicitly alien, yet intimately physical embodiments of divine power in the natural world. Taken together, these poems-one a metrical romance, the other alliterative-show how interests in waterscapes crossed boundaries within the muddy genre of romance itself, and reveal that water upsets such human categories as family and property. Tarns, rivers, and seas turn human bodies, instead, into their possessions; the disturbing experience of that dehumanizing process should, these texts imply, wear the world, its history, and its bonds away, until even the greatest knights or ladies are left alone with watery forms beyond the pale of human understanding. © 2018 The Author(s).
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/049-894-901-510-053, pop00161
Keywords: dept.eng; peer-reviewed

The Rise of Silas Lapham: Authoritative Text, Contexts, Criticism - Howells, William Dean (W.W. Norton & Company, Inc., 2018)
Keywords: Fiction; Fiction; Domestic fiction; Psychological fiction; Boston (Mass.); Fiction; Rich people; Fiction; Socialites; Howells; William Dean; 1837-1920. Rise of Silas Lapham; Businessmen; dept.eng

Science and technology in Hawthorne’s short fiction - Ellis, Scott (Nathaniel Hawthorne in the College Classroom: Contexts, Materials, and Approaches, 2018)
This new work is currently the only book devoted to the teaching of one of the most canonical and frequently taught American authors.In addition to a Preface by the noted Hawthorne scholar Larry J. Reynolds [University Distinguished Professor and Thomas Franklin Mayo Professor of Liberal Arts Department of English Texas A&M University] the contributors include well-known and rising teacher-scholars who offer theoretical and pedagogical approaches to Hawthorne's four published novels and a wide range of his short stories.The specially commissioned essays are designed to help teachers meet students at points of genuine interest and need. They incorporate biographical, literary, historical, and multidisciplinary scholarship. The studies are further grounded in specific contexts such as literature surveys, interdisciplinary humanities courses, upper division literature seminars, and study abroad courses.Special emphasis is given to the issues of gender, science, and visual culture (including film adaptations). Offering both theoretical and practical classroom resources, this anthology confirms the continued vitality of Hawthorne's work - his critiques of religious and moral authority are more relevant than ever in today's global political environment - even as it showcases how today's "Hawthorne" is more of a diverse amalgam of texts and perspectives than ever before. Given its diversity of approaches and authors (including essayists from Germany, Israel, and Sweden), Nathaniel Hawthorne in the College Classroom charts new paths for reading and teaching Hawthorne in the 21st century.
Keywords: dept.eng

Reaping something new: African American transformations of Victorian literature. - Baraw, Charles (Journal of British Studies, 2018)
0 citations (Crossref) [2023-10-31] Citation Key Alias: barawDanielHackReaping2018 tex.eissn: [object Object] tex.unique-id: [object Object]
Keywords: dept.eng; peer-reviewed

States of the Union - Papa, Michaela (Mascot Books, 2018)
In nonfiction, poetry, short fiction, artwork, and detailed interviews, States of the Union collects reflections from everyday Americans on the 2016 presidential election. -Publisher Web Site.
Keywords: 2016; Election; Presidents; United States; dept.eng; faculty_collection

Can we be part of the pride? Reading animals through comics in the undergraduate classroom - Baraw, Charles; Smyth, Andrew (Animal comics: Multispecies storyworlds in graphic narratives, 2017)
Animal characters abound in graphic narratives ranging from Krazy Kat and Maus to WE3 and Terra Formars. Exploring these and other multispecies storyworlds presented in words and images, Animal Comics draws together work in comics studies, narrative theory, and cross-disciplinary research on animal environments and human-animal relationships to shed new light on comics and graphic novels in which animal agents play a significant role. At the same time, the volume's international team of contributors show how the distinctive structures and affordances of graphic narratives foreground key questions about trans-species entanglements in a more-than-human world. The writers/artists covered in the book include: Nick Abadzis, Adolpho Avril, Jeffrey Brown, Sue Coe, Matt Dembicki, Olivier Deprez, J. J. Grandville, George Herriman, Adam Hines, William Hogarth, Grant Morrison, Osamu Tezuka, Frank Quitely, Yu Sasuga, Charles M. Schultz, Art Spiegelman, Fiona Staples, Ken'ichi Tachibana, Brian K. Vaughan, and others.
Google-Books-ID: 8rU7DwAAQBAJ
Keywords: Art / Subjects & Themes / Landscapes & Seascapes; Comics & Graphic Novels / Literary; Humor / Form / Comic Strips & Cartoons; Literary Criticism / Comics & Graphic Novels; dept.eng

Spleen elegy - Labbe, Jason (BlazeVOX [books], 2017)
Let’s twin and twine together two primary aspects of how America can see herself—the good atoms of Whitman’s leaves of grass, and the engines humming their freedom on the highways that cut across those 19th century fields. Now, Jason Labbe well knows, as Whitman’s atoms become pixels, we find ourselves at a crossroads, learning again and again the consequences of “the indescribable way you shape / a past of little use.” Seeking to find that law or logic to shattering, be it in the memory-echo of personal trauma caught on infinite loop in the mind, or be it the dismal virtualities of the post-modern ether, the poems of Spleen Elegy unfold their rueful nostalgia: “I have something accurate to say that lacks perspective.” That may well be the very accuracy we most need, riding the routes of America, the byways and frontage roads, seeking anyone who is willing for a poem or two to see. —Dan Beachy-Quick "A chunk of broken tar”—that's the color of this book. And the sound of this book is "a train in the static." Its poems count time in "decaseconds of dusk." To read this book is to feel the uneasy passivity and unerring stuckness, the particular absurdity, of certain citizens stuck in this millennium. So many lines made me laugh. And sigh. But not cry. Jason Labbe is great at melancholy. Baudelaire's mosquito is definitely here: "I am Past / who passing lit and sucked your life and left." The future is unthinkable and unalterable. Except. Except! Lucretius' swerve is also here. Atoms may veer randomly, which is extra significant in a book that takes place mostly on the road. "My sutures are beautiful as a tread pattern," he says, and it is easy (and dangerous) to fall in love with Labbe's strangled version of optimism. —Darcie Dennigan
Keywords: dept.eng

Foucault, confession, and Donne - Dodson, Joel M. (Forms of faith, 2017)
Keywords: dept.eng

Empathy as Orientation Rather than Feeling: Why Empathy Is Ethically Complex - Larocco, Steve (Exploring Empathy, 2017)
"Empathy as Orientation Rather than Feeling: Why Empathy Is Ethically Complex" published on 01 Jan 2017 by Brill | Rodopi.
Keywords: dept.eng

Hawthorne, a pilgrimage to Salem, and the poetics of literary tourism - Baraw, Charles (Canadian Review of American Studies, 2017)
From the 1830s to the end of his career, Nathaniel Hawthorne used the tropes of aesthetic tourism to call out, or interpellate, the reader as a literary tourist. In many cases, Hawthorne’s focalizi...
2 citations (Crossref) [2023-10-31]
Keywords: "Alice Doane's appeal" Caroline Gilman; Literary tourism; Narrative poetics; Nathaniel Hawthorne; Samuel Gilman; Touristic poetics; dept.eng